Adrenal crisis in a 14-year-old boy 12 years after hematopoietic stem cell transplantation - Penger, Theresa; Albrecht, Andrea; Marx, Martin; Stachel, Daniel; Metzler, Markus; Dörr, Helmuth-Günther (Endocrinology, Diabetes and Metabolism Case Reports, 2018)
We report on a boy of Albanian descent with the history of juvenile myelomonocytic leukemia (JMML). JMML was diagnosed at the age of 17 months and treated by hematopoietic stem cell transplantation (HSCT). At the age of 14.3 years, about 12 years after HSCT, he was hospitalized with an adrenal crisis. Hormone findings were consistent with primary adrenal insufficiency. Autoimmune adrenalitis was confirmed by positive autoantibodies against 21-hydroxylase and adrenal tissue. Since autoimmune Hashimoto thyroiditis was already known from the age of 9 years, we assume that both diseases are part of the spectrum of autoimmune polyglandular syndrome (APS) type 2. APS type 2 is a rare endocrine disease characterized by Addison's disease along with autoimmune thyroid disease and/or type 1 diabetes. Learning points: Endocrine sequelae after hematopoietic stem cell transplantation (HSCT) are common and can develop over a long period.Primary adrenal insufficiency after HSCT is absolutely rare.The combination of adrenal autoimmune disease and Hashimoto thyroiditis is consistent with autoimmune polyglandular syndrome type 2.
EVALuna2:35483

Adrenarche and pubarche in girls with turner syndrome during growth-promoting therapy with human growth hormone - Dörr, Helmuth-Günther; Penger, Theresa; Marx, Martin; Rauh, Manfred; Oppelt, Patricia; Völkl, Thomas (BMC Endocrine Disorders, 2019)
Background: Data on adrenarche and pubarche in girls with Turner syndrome (TS) are inconsistent in the literature. Methods: The cohort consisted of 94 girls and young women with TS born between 1971 and 2001 (age range: 3.1-23.2 yrs.), who were treated with human growth hormone and regularly presented at our outpatient clinic every 4 to 6 months.The longitudinal data of all patients were ascertained retrospectively from patient charts. The data collection ended in January 2016. Adrenarche was assessed by serum DHEAS levels and pubertal status by Tanner stages. Pubarche was defined as the appearance of pubic hair (PH2), whereas spontaneous puberty was defined as Tanner stage B2. The patients were retrospectively subdivided in two groups with regard to pubertal development: group 1 (n = 21) with spontaneous puberty and group 2 (n = 70) with induced puberty. Since blood samples were not taken at every visit, we generated seven groups according to the age of the children at which the blood samples were taken: 3-5, 5-7, 7-9, 9-11, 11-13, 13-15, and 15-17 yrs. Serum DHEAS and follicle-stimulating hormone (FSH) levels were measured by chemiluminescence immunoassay and compared with those of a control group of healthy girls. Results: Adrenarche started in TS girls between 5 and 7 years. TS girls had higher DHEAS levels than the control group, with statistically significant differences in the age groups 7 to 17 years. No differences were determined between the TS girls with spontaneous puberty and those with POI. TS girls in group 2 reached the Tanner stages PH2 (p < 0.04), PH3 (p < 0.01), PH4 and PH5 (p < 0.001) markedly later than TS girls in group 1. Conclusions: The onset of adrenarche in girls with TS undergoing GH therapy does not differ from that in healthy girls. However, adrenarche is more pronounced in girls with TS. There is no difference in DHEAS levels between the TS girls with spontaneous puberty and the TS girls with primary ovarian insufficiency (POI), while the tempo of pubarche is markedly slower in the girls with POI.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Adrenarche; DHEAS; Primary ovarian insufficiency; Turner syndrome

Approach to the subject of tall stature in clinical practice Das große Kind in der Praxis - Dörr, Helmuth-Günther (Pädiatrische Praxis, 2020)
The paediatrician should be able to distinguish the causes of tall stature and to differentiate the normal variants from the pathological forms. Any kind of uncertainty during diagnosis should be clarified with the assistance of a paediatric endocrinologist. During treatment of children with overgrowth syndromes, a close cooperation with other special disciplines (e. g. human genetics, neuropaediatrics, and paediatric oncology) is necessary. A medical therapy is generally possible. The better acceptance of tall people in today's society has changed the indication for the treatment. Due to reports on fertility problems in tall girls after treatment, this therapy is no longer recommended. The method of bilateral percutaneous epiphysiodesis around the knee could be a surgical alternative.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Diagnostic guidance; Normal variants; Overgrowth; Tall stature

Betreuung von Kindern und Jugendlichen mit M. Basedow in einem endokrinologischen Zentrum - Penger, Theresa; Albrecht, Andrea; Marx, Martin; Jüngert, Jörg M.; Kuwert, Torsten; Dörr, Helmuth-Günther (Monatsschrift Kinderheilkunde, 2019)
Background: Graves’ disease is rare in childhood and adolescence. While the criteria for diagnosis are clearly defined, there are controversial discussions in the literature regarding the optimal treatment modality. Objective: The aim of the study was to retrospectively analyze the treatment and long-term course of patients with Graves’ disease who were under the care of this outpatient department of pediatric endocrinology between 2000 and 2015. Material and methods: The data of 50 children and adolescents (40 female, 10 male) aged between 4.5 and 17.6 years (median 12.4 years) were evaluated. The patient history, height, weight and laboratory values were documented at the initial presentation and at every outpatient visit. The duration to achievement of euthyroidism (remission), the time until attempted withdrawal, the duration of remission, the time of recurrence and the time and type of a final treatment were also documented. To calculate thyroid volume (SDS) values, the data of Kromeyer-Hauschild et al. were used as references for height and BMI and for the sonographically measured thyroid volume the data of the German National Health Examination Survey for Children and Adolescents (KiGGS) were used. Results (median values): The diagnosis was made 6 months after the onset of symptoms at the age of 12.4 years. Serum thyroid-stimulating hormone (TSH) levels were suppressed, free tri-iodothyronine (fT3, 21.6 pmol/l; normal range 3.5–8.1), free thyroxine (fT4, 48.3 pmol/l; 7.6–17.7), and TSH-receptor antibody (TRAB, 9.4 U/l; <1.5) were elevated. At diagnosis 28 children had goiter (+5.9 SDS) and 15 patients developed a goiter during the further course. All patients primarily received thiamazole (n = 34) or carbimazole (n = 16) and 18 patients a beta blocker. During the course 96% received dual therapy (antithyroid drug plus L‑T4) and 9 patients are still receiving primary treatment. Thus, 41 patients could be assessed with respect to the long-term course. The treatment did not affect the size of the thyroid gland. A withdrawal trial was performed in 33 patients at 32 months, including 6 patients receiving treatment for <24 months and 11 patients receiving treatment for more than 36 months. Thyroidectomy was performed in 8 patients on drug treatment without a withdrawal trial due to the increasing goiter. After the end of the thyrostatic therapy, 17 patients achieved full remission (no recurrence of hyperthyroidism after completion of drug treatment) and 8 patients currently have a remission duration ≥12 months. Recurrence treatment was initiated in 7 patients after the first remission and 9 patients underwent thyroidectomy. Conclusion: The high remission rate was positively correlated with the treatment duration. The dual therapy regimen might also affect the outcome. The size of the thyroid gland was unchanged during treatment. The extent of TRAB levels at the time of the withdrawal trial did not affect the long-term outcome. In all cases with a rapid goiter progression, an early thyroidectomy should be performed.
CRIS-Team Scopus Importer:2020-02-21
Keywords: Hyperthyroidism; Long-term outcome; Single center; Therapeutic options

Birth Size in Neonates with Congenital Adrenal Hyperplasia due to 21-hydroxylase Deficiency - Dörr, Helmuth-Günther; Penger, Theresa; Albrecht, Andrea; Marx, Martin; Völkl, Thomas (JCRPE Journal of Clinical Research in Pediatric Endocrinology, 2019)
Objective: Classic congenital adrenal hyperplasia (CAH) secondary to 21-hydroxylase deficiency is characterized by increased prenatal adrenal androgen secretion. There are a small number of reports in the literature showing higher birth weight and length in CAH newborns.
CRIS-Team WoS Importer:2019-03-06

Blood Pressure in a Large Cohort of Children and Adolescents With Classic Adrenal Hyperplasia (CAH) Due to 21-Hydroxylase Deficiency - Bonfig, Walter; Roehl, Friedrich-Wilhelm; Riedl, Stefan; Dörr, Helmuth-Günther; Bettendorf, Markus; Braemswig, Juergen; Schoenau, Eckhard; Riepe, Felix; Hauffa, Berthold; Holl, Reinhard W.; Mohnike, Klaus (American Journal of Hypertension, 2016)
BACKGROUND: Data on blood pressure (BP) in children and adolescents with classic congenital adrenal hyperplasia (CAH) due to 21-hydroxylase deficiency are conflicting in the literature. PATIENTS AND METHODS: BP data of n = 716 children and adolescents (aged 3-18 years) from a national CAH database were analyzed. BP data were adjusted for height and compared to contemporary national reference data. A systolic and diastolic BP above the 95th centile was defined as hypertensive. RESULTS: Overall prevalence of hypertension was 12.5%. Prevalence of hypertension was higher in younger children than in adolescents (18.5% vs. 4.9%). Until 8 years of age, fludrocortisone dose/m(2)/day correlated significantly with BP in regression analysis (P < 0.0001). BP correlated significantly with body mass index standard deviation score (BMI-SDS) (P < 0.0001), but not with hydrocortisone dose. In patients with salt-wasting CAH, BMI-SDS and BP were significantly higher compared to patients with simple virilising CAH, P < 0.01. CONCLUSION: Especially young CAH children seem to be at risk for-most likely transient-hypertension, since the prevalence of hypertension decreases with age. In children up to 8 years of age, the used fludrocortisone dose is a significant risk factor for hypertension. Therefore we recommend accurate measurement of BP and careful fludrocortisone dosing in children with CAH.
EVALuna2:34016

Caring for a Child with Congenital Adrenal Hyperplasia Diagnosed by Newborn Screening: Parental Health-Related Quality of Life, Coping Patterns, and Needs - Rautmann, Laura; Witt, Stefanie; Theiding, Christoph; Odenwald, Birgit; Nennstiel-Ratzel, Uta; Dörr, Helmuth-Günther; Quitmann, Julia Hannah (International Journal of Environmental Research and Public Health, 2023)
Diagnosing a child by newborn screening with classic congenital adrenal hyperplasia due to 21-hydroxylase deficiency (CAH) causes multiple challenges for the affected parents and the whole family. We aimed to examine the health-related Quality of Life (HrQoL), coping, and needs of parents caring for a child with CAH to develop demand-responsive interventions for improving the psychosocial situation of affected families. In a retrospective cross-sectional design, we assessed HrQoL, coping patterns, and the needs of parents caring for a CAH-diagnosed child using specific questionnaires. Data of 59 families with at least one child diagnosed with CAH were analyzed. The results show that mothers and fathers in this study reached significantly higher HrQoL scores compared to reference cohorts. Decisive for the above-average parental HrQoL were effective coping behaviors and the parental needs being met. These findings verify the importance of helpful coping patterns and rapid fulfillment of parental needs for maintaining a good and stable HrQoL of parents with a child diagnosed with CAH. It is crucial to strengthen the parental HrQoL to build a reasonable basis for a healthy upbringing and improve the medical care of CAH-diagnosed children.
CRIS-Team Scopus Importer:2023-03-24
Keywords: 21-hydroxylase deficiency; congenital adrenal hyperplasia; newborn screening; parental coping; parental needs; psychological stress; rare disease

Children with classic congenital adrenal hyperplasia experience salt loss and hypoglycemia: evaluation of adrenal crises during the first 6 years of life - Odenwald, Brigitte; Nennstiel-Ratzel, Uta; Dörr, Helmuth-Günther; Schmidt, Heinrich; Wildner, Manfred; Bonfig, Walter (European Journal of Endocrinology, 2016)
OBJECTIVE: To evaluate adrenal crises after the start of treatment up to the age of 6 years in children with classic congenital adrenal hyperplasia (CAH). DESIGN: Analysis of data extracted from a population-based prospective long-term follow-up study of children detected in neonatal screening. METHODS: Data of 102 Bavarian children with classic CAH due to 21-hydroxylase deficiency were analyzed, using parental questionnaires and medical reports. Parent-reported hospital admissions of children diagnosed with acute health impairment were included in the analysis if salt loss (hyponatremia) or hypoglycemia was documented in the discharge summary. RESULTS: A total of 74 children (72.5%) had no report of hospital admissions with salt loss or hypoglycemia during the observational period. However, in 27.5% of the children, 22 salt-wasting crises (seven of these also with low blood glucose) and 16 hypoglycemic episodes without salt loss were reported. Furthermore, the cumulative incidence for seizures was elevated; 13 children experienced seizures during hyponatremia or hypoglycemia. Most adrenal crises were triggered by infections, often with inappropriate emergency management, but in 11 cases hypoglycemia occurred unexpectedly, without evidence of severe illness and without any management errors. Frequency of adrenal crises was 6.5 per 100 patient years (95% CI: 4.6-8.8). CONCLUSIONS: Crisis prevention remains a permanent challenge for families and physicians caring for children with classic CAH. Expert care and compliance with emergency recommendations are crucial. Further research on the interactions among glucocorticoid deficiency, adrenomedullary dysfunction, and glucose metabolism is necessary for the prevention of hypoglycemia, especially in young CAH patients.
EVALuna2:33872

Classic Congenital Adrenal Hyperplasia due to 21-Hydroxylase-Deficiency: 13 Years of Neonatal Screening and Follow-up in Bavaria - Odenwald, B.; Dörr, Helmuth-Günther; Bonfig, W.; Schmidt, H.; Fingerhut, R.; Wildner, M.; Nennstiel-Ratzel, U. (Klinische Pädiatrie, 2015)
21-Hydroxylase deficient (21-OHD) classic congenital adrenal hyperplasia (CAH) is a potentially lethal inherited endocrine disorder. It is included in many neonatal screening programs to prevent morbidity and mortality from salt-wasting and to reduce long-term health problems. This paper presents a population-based evaluation of CAH screening quality and outcome in Bavaria between 1999 and 2011 including long-term follow-up of patients.Screening process quality, clinical complications during the neonatal period, treatment and development of patients up to the age of 4 years were analysed.Among 1 420 102 screened infants, 114 cases of 21-OHD classic CAH were detected (prevalence 1:12 457). Mean age at start of treatment was 7 days. However, in 29 cases (25.4%), age at start of treatment was 12 days or more. The frequency of neonatal salt-wasting increased with age at start of treatment, but all neonatal salt-wasting episodes and crises were managed successfully. Up to the age of 4 years, developmental assessment of the CAH cohort yielded normal results.Epidemiological and screening effectiveness results are in keeping with other publications. For the most part, screening process times were compliant with guidelines. The Bavarian CAH screening and tracking system proved successful, but there were process delays and complications which might have been avoidable. The outcome supports the benefits of CAH screening, but further research is necessary to increase CAH screening effectiveness and to evaluate long-term effects.
EVALuna2:18918

Clinical relevance of systematic phenotyping and exome sequencing in patients with short stature - Hauer, Nadine; Popp, Bernt; Schoeller, Eva; Schuhmann, Sarah; Heath, Karen E.; Hisado-Oliva, Alfonso; Klinger, Patricia; Kraus, Cornelia; Trautmann, Udo; Zenker, Martin; Zweier, Christiane; Wiesener, Antje; et al. (Genetics in Medicine, 2018)
PurposeShort stature is a common condition of great concern to patients and their families. Mostly genetic in origin, the underlying cause often remains elusive due to clinical and genetic heterogeneity.MethodsWe systematically phenotyped 565 patients where common nongenetic causes of short stature were excluded, selected 200 representative patients for whole-exome sequencing, and analyzed the identified variants for pathogenicity and the affected genes regarding their functional relevance for growth.ResultsBy standard targeted diagnostic and phenotype assessment, we identified a known disease cause in only 13.6% of the 565 patients. Whole-exome sequencing in 200 patients identified additional mutations in known short-stature genes in 16.5% of these patients who manifested only part of the symptomatology. In 15.5% of the 200 patients our findings were of significant clinical relevance. Heterozygous carriers of recessive skeletal dysplasia alleles represented 3.5% of the cases.ConclusionA combined approach of systematic phenotyping, targeted genetic testing, and whole-exome sequencing allows the identification of the underlying cause of short stature in at least 33% of cases, enabling physicians to improve diagnosis, treatment, and genetic counseling. Exome sequencing significantly increases the diagnostic yield and consequently care in patients with short stature.
EVALuna2:34628

Cullin 7 and Fbxw 8 expression in trophoblastic cells is regulated via oxygen tension: Implications for intrauterine growth restriction - Fahlbusch, Fabian; Dawood, Yousif Louay; Hartner, Andrea; Menendez-Castro, Carlos; Nögel, Stephanie; Tzschoppe, Anja; Schneider, Holm; Strissel, Pamela; Beckmann, Matthias; Schleussner, Ekkehard; Rübner, Matthias; Dörr, Helmuth-Günther; et al. (Journal of Maternal-Fetal & Neonatal Medicine, 2012)
Objective: The F-box protein Fbxw8 is a cofactor of Cullin 7 (Cul7), which regulates protein transfer to the proteasome and cell growth. Cul7 or Fbxw8 deficiency is associated with intrauterine growth restriction (IUGR) due to abnormal placental development leading to poor oxygen supply to the fetus. We studied the role of hypoxia for Fbxw8 and Cul7 expression in trophoblastic cells. Methods: Immunomagnetic bead-separated extravillous trophoblast (EVT) and villous trophoblast (VT) and trophoblast cell lines were incubated with 1 or 8% O2. Fbxw8 and Cul7 expression was determined in IUGR versus matched control placentas. Results: Fbxw8 was expressed uniformly in trophoblasts, whereas Cul7 expression was most prominent in trophoblast cell lines. Hypoxia reduced expression of Cul7 and Fbxw8 in all trophoblastic cells, except for villous trophoblasts. In vivo, Cul7 and Fbxw8 were detected in syncytiotrophoblast cells, VT, and EVT cells. Although no significant changes in expression levels of Fbxw8 or Cul7 were noted in IUGR compared with control placentas, Fbxw8 expression correlated negatively with gestational age in the control, but not in the IUGR group. Conclusion: Fbxw8 and Cul7 expression reveals a complex regulation in trophoblastic cells. Our findings suggest that dysregulation of Cul7 and Fbxw8 expression might affect trophoblast turnover in IUGR. © 2012 Informa UK, Ltd.
CRIS-Team Scopus Importer:2020-07-01
Keywords: Cul7; Fbxw8; IUGR; Oxygen; Placenta; Trophoblast

Current clinical practice of prenatal dexamethasone treatment in at risk pregnancies for classic 21-hydroxylase deficiency in Europe - Nowotny, Hanna F.; Neumann, Uta; Tardy-Guidollet, Veronique; Ahmed, S. Faisal; Baronio, Federico; Battelino, Tadej; Bertherat, Jerome; Blankenstein, Oliver; Bonomi, Marco; Bouvattier, Claire; De La Perriere, Aude Brac; Brucker, Sara; et al. (HORMONE RESEARCH IN PAEDIATRICS, 2021)
CRIS-Team WoS Importer:2021-10-08

Das nicht klassische adrenogenitale Syndrom mit 21-Hydroxylase-Defekt bei Kindern und Jugendlichen - Dörr, Helmuth-Günther; Schulze, Nadja (Pädiatrische Praxis, 2020)
Non-classical AGS with 21-hydroxylase defect is a common monogenetic disorder that is often not diagnosed or diagnosed too late. The leading clinical symptom in girls is the premature pubarche before the 8th birthday. For diagnostic purposes, 17-OHP should be measured in serum in the morning for children in the first step and in the follicular phase for menstruating girls. The gold standard in diagnostics is the ACTH test, whereby cortisol should also be determined in the serum in addition to 17-OHP. The laboratory chemical diagnosis should in any case be confirmed by molecular genetic analysis. Drug therapy in children with hydrocortisone is carried out in a low dose if the clinical symptoms are progressive and, above all, there is a poor prognosis of the final size due to the acceleration of bone age. If a therapy with glucocorticoids is carried out, then an emergency ID card should also be issued.
CRIS-Team Scopus Importer:2021-04-19
Keywords: 17-OHP; ACTH test; Cortisol; CYP21A2; Premature pubarche

Das nicht klassische Adrenogenitale Syndrom mit 21-Hydroxylase-Defekt bei Kindern und Jugendlichen - Dörr, Helmuth-Günther; Schulze, Nadja (gynäkologische praxis, 2021)
Non-classical AGS with 21-hydroxylase defect is a common monogenetic disorder that is often not diagnosed or diagnosed too late. The leading clinical symptom in girls is the premature pubarche before the 8th birthday. For diagnostic purposes, 17-OHP should be measured in serum in the morning for children in the first step and in the follicular phase for menstruating girls. The gold standard in diagnostics is the ACTH test, whereby cortisol should also be determined in the serum in addition to 17-OHP. The laboratory chemical diagnosis should in any case be confirmed by molecular genetic analysis. Drug therapy in children with hydrocortisone is carried out in a low dose if the clinical symptoms are progressive and, above all, there is a poor prognosis of the final size due to the acceleration of bone age. If a therapy with glucocorticoids is carried out, then an emergency ID card should also be issued.
CRIS-Team Scopus Importer:2024-12-16
Keywords: 17-OHP; ACTH test; cortisol; CYP21A2; premature pubarche

Detection of expressional changes induced by intrauterine growth restriction in the developing rat mammary gland via exploratory pathways analysis - Beinder, Lea; Fährmann, Nina; Wachtveitl, Rainer; Winterfeld, Ilona; Hartner, Andrea; Menendez-Castro, Carlos; Rauh, Manfred; Ruebner, Matthias; Hübner, Hanna; Nögel, Stephanie; Dörr, Helmuth-Günther; Rascher, Wolfgang; et al. (PLoS ONE, 2014)
Intrauterine growth restriction (IUGR) is thought to lead to fetal programming that in turn contributes to developmental changes of many organs postnatally. There is evidence that IUGR is a risk factor for the development of metabolic and cardiovascular disease later in life. A higher incidence of breast cancer was also observed after IUGR. This could be due to changes in mammary gland developmental pathways. We sought to characterise IUGR-induced alterations of the complex pathways of mammary development at the level of the transcriptome in a rat model of IUGR, using pathways analysis bioinformatics.We analysed the mammary glands of Wistar rats with IUGR induced by maternal low protein (LP) diet at the beginning (d21) and the end (d28) of pubertal ductal morphogenesis. Mammary glands of the LP group were smaller in size at d28, however did not show morphologic changes. We identified multiple differentially expressed genes in the mammary gland using Agilent SurePrint arrays at d21 and d28. In silico analysis was carried out using Ingenuity Pathways Analysis. In mammary gland tissue of LP rats at d21 of life a prominent upregulation of WT1 and CDKN1A (p21) expression was observed. Differentially regulated genes were associated with the extracellular regulated kinase (ERK)-1/-2 pathway. Western Blot analysis showed reduced levels of phosphorylated ERK-1/-2 in the mammary glands of the LP group at d21. To identify possible changes in circulating steroid levels, serum LC-Tandem mass-spectrometry was performed. LP rats showed higher serum progesterone levels and an increased corticosterone/dehydrocorticosterone-ratio at d28.Our data obtained from gene array analysis support the hypothesis that IUGR influences pubertal development of the rat mammary gland. We identified prominent differential regulation of genes and pathways for factors regulating cell cycle and growth. Moreover, we detected new pathways which appear to be programmed by IUGR.
EVALuna2:17429

Differential effects of low birthweight and intrauterine growth restriction on umbilical cord blood insulin-like growth factor concentrations - Tzschoppe, Anja; Riedel, Christina; Von Kries, Ruediger; Struwe, Ellen; Rascher, Wolfgang; Dörr, Helmuth-Günther; Beckmann, Matthias; Schild, Ralf L.; Goecke, Tamme W.; Flyvbjerg, Allan; Frystyk, Jan; Doetsch, Joerg (Clinical Endocrinology, 2015)
Alterations in the growth hormone-insulin-like growth factor (IGF) axis have been considered as a causal factor for intrauterine growth restriction (IUGR) and for the increased risk of metabolic disease in later life. We compared members of the IGF axis in umbilical cord blood between IUGR neonates, small for gestational age without foetal restriction (SGA) and appropriate for gestational age (AGA) neonates.Prospective controlled multicenter study.Sixteen ultrasound-proven IUGR, 8 SGA and 40 AGA neonates.Concentrations of total IGF-I and total IGF-II by immunoassays, bioactive IGF by cell-based bioassay and IGFBP-I in mixed venous and arterial umbilical cord blood samples at birth. Auxological parameters at birth.IGF-I concentrations in IUGR [17·7 ?g/l (CI 13·8;21·6)] were clearly below those in AGA [48·3 ?g/l (CI 43·7;52·9)] and SGA neonates [36·0 ?g/l (CI 26·6;45·4)]. IGF-II levels were significantly reduced in IUGR [201·4 ?g/l (CI 190·2;212·6)] compared to AGA neonates [231·2 ?g/l (CI 220·6;241·9)]. A trend for lower IGF-II concentrations was observed in IUGR when compared to SGA neonates [232·0 ?g/l (CI 207·2;256·8)]. These differences could not be explained by confounding. For IGFBP-1, a trend towards higher values in IUGR was observed.Low IGF-I cord blood concentrations in hypotrophic neonates after IUGR might not only result from low birthweight per se, but also reflect prenatal placental environment. Alterations of the IGF axis could be in the causal pathway of IUGR and thus constitute a potential surrogate marker for IUGR in the assessment of foetal programming.
EVALuna2:17440

Diffuse Encephalopathy Associated with Isolated Cerebral Langerhans Cell Histiocytosis - Rompel, Oliver; Buslei, Rolf; Hammon, Matthias; Dörr, Helmuth-Günther; Chada, Martin; Nikkhah, Guido; Uder, Michael; Trollmann, Regina (Pediatric Neurology, 2016)
Langerhans cell histiocytosis is a rare disease of the monocyte-macrophage system. Abnormalities of the hypothalamic-pituitary region are common in individuals with central nervous system involvement.This six-year-old boy developed rapidly progressive aggressive behavior, central diabetes insipidus, and repeated complex partial seizures. Magnetic resonance imaging revealed a diffuse leukoencephalopathy-like pattern and numerous infratentorial and supratentorial granulomatous nodules in the brain parenchyma along with infundibular and hypothalamic mass lesions. Stereotactic serial biopsies enabled histopathologic and immunohistochemical diagnosis of Langerhans cell histiocytosis.Similar MRI findings have rarely been described in the literature. These findings represent part of the broad neuroradiological spectrum of Langerhans cell histiocytosis of the nervous system in children.
EVALuna2:7341

DYNC2LI1 mutations broaden the clinical spectrum of dynein-2 defects - Keßler, Kristin; Wunderlich, Ina; Uebe, Steffen; Falk, Nathalie; Gießl, Andreas; Brandstätter, Johann Helmut; Popp, Bernt; Klinger, Patricia; Ekici, Arif Bülent; Sticht, Heinrich; Dörr, Helmuth-Günther; Reis, André; et al. (Scientific Reports, 2015)
Skeletal ciliopathies are a heterogeneous group of autosomal recessive osteochondrodysplasias caused by defects in formation, maintenance and function of the primary cilium. Mutations in the underlying genes affect the molecular motors, intraflagellar transport complexes (IFT), or the basal body. The more severe phenotypes are caused by defects of genes of the dynein-2 complex, where mutations in DYNC2H1, WDR34 and WDR60 have been identified. In a patient with a Jeune-like phenotype we performed exome sequencing and identified compound heterozygous missense and nonsense mutations in DYNC2LI1 segregating with the phenotype. DYNC2LI1 is ubiquitously expressed and interacts with DYNC2H1 to form the dynein-2 complex important for retrograde IFT. Using DYNC2LI1 siRNA knockdown in fibroblasts we identified a significantly reduced cilia length proposed to affect cilia function. In addition, depletion of DYNC2LI1 induced altered cilia morphology with broadened ciliary tips and accumulation of IFT-B complex proteins in accordance with retrograde IFT defects. Our results expand the clinical spectrum of ciliopathies caused by defects of the dynein-2 complex.
EVALuna2:9281

Effect of Psychosocial Factors on Growth - Gohlke, Bettina C.; Bettendorf, Markus; Binder, Gerhard; Hauffa, Berthold; Reinehr, Thomas; Dörr, Helmuth-Günther; Wölfle, Joachim (Klinische Pädiatrie, 2021)
Background Genes, hormones and factors such as nutrition and psychosocial environment affect growth. Objective What is the significance of various psychosocial factors on growth? Methods Evaluation of results of a working meeting of paediatric endocrinologist with current literature research. Results Psychosocial deprivation in children can be associated with growth hormone deficiency (GHD) and short stature. GHD can be reversed by a change of environment and psychosocial support. War and migration are often associated with underweight, growth disturbances and poor health care. These factors can improve after the end of conflicts, but children often remain too short. Consumption of alcohol or opiates during pregnancy are associated with lower birth weight and increased risk of early and small for gestational age (SGA) childbirth. Children with attention deficit hyperactivity disorder show a slight slowdown in growth after they started stimulant therapy. However, they reach normal adult height. Conclusions In children with idiopathic short stature, psychosocial causes should be taken into account in the differential diagnosis. Notably there is an increased risk of growth disturbances in children from conflict regions or after prenatal drug exposure.
CRIS-Team WoS Importer:2021-12-24

Ektope Lage einer Schilddrüse im Zungengrund – Zufallsdiagnose bei einem 6‑jährigen Mädchen - Albrecht, Andrea; Penger, Theresa; Marx, Martin; Jüngert, Jörg M.; Kuwert, Torsten; Dörr, Helmuth-Günther (Monatsschrift Kinderheilkunde, 2020)
Background: An ectopic thyroid gland is a rare anomaly due to the incomplete descent of the thyroid gland during the embryonic developmental migration process. The ectopic thyroid tissue is normally located in the area from the tongue to the diaphragm but lingual and sublingual locations preferentially occur. In a child with congenital hypothyroidism, which was detected during neonatal screening, the ectopic gland could be diagnosed during the further clarification. Case report: This article reports on the case of a girl who was presented to the pediatrician for clarification of chronic abdominal pain at the age of 6 years and 3 months. As an incidental finding the pediatrician diagnosed a subclinical hypothyroidism (serum TSH 23.3 mU/l, fT3 and fT4 normal) and initiated treatment with L‑thyroxine (L-T4). The psychomotor, growth and weight development had always been age-appropriate. At the initial presentation in this outpatient department the girl was 6 years and 5 months old, was clinically and biochemically euthyroid, and the body measurements were normal. The thyroid autoantibodies were inconspicuous. The ultrasound scan revealed a small lingual thyroid-like tissue (volume 0.9 ml) with no thyroid tissue in the typical site. A thyroid scintigraphy confirmed the diagnosis. Under the weight-adapted medication with L‑thyroxine the patient never developed symptoms of hypothyroidism and the volume of the lingual thyroid did not increase. The patient is currently 11 years and 8 months old (height 146.9 cm, weight 33.3 kg, Tanner stage B 2) and attends a grammar school. Conclusion: A thyroid gland at the base of the tongue is a rare cause of latent hypothyroidism and is difficult to diagnose when there is a lack of clinical symptoms. It can be detected at any age as an incidental finding.
CRIS-Team Scopus Importer:2020-05-05
Keywords: Ectopic lingual thyroid; Incidental finding; Rare disease; Subclinical hypothyroidism; Thyroid ultrasound

Endocrine Late Effects in Young Cancer Patients: Thyroid Gland - Brabant, Georg; Dörr, Helmuth-Günther (Springer International Publishing, 2020)
The increased survival rates after pediatric oncological therapy result in an increase in the number of patients showing late effects of tumor therapy. Thyroid function and proliferation disorders in particular are common sequelae of treatment of malignant tumors in childhood and adolescence. They predominantly occur after irradiation of the head and neck and the thyroid glands. The clinical symptoms depend on the thyroid hormone status. The current guidelines on endocrine late effects in these patients are endorsed by the working group of the Scientific Medical Specialist Societies (AWMF). Based on standardized evaluation of currently available literature, this review article summarizes the approaches for late sequelae of tumor therapy on thyroid glands. The specific group of long-term survivors of younger ages, like children, adolescents, and young adults, are constantly growing due to enhanced diagnostic tools and more effective treatment strategies. Thus, their specific survivorship care needs to be addressed in a holistic approach. Whilst a lot of scientific work has focused on somatic late effects of survivors, a growing body of research has recently been directed towards psychosocial outcomes of survivors. A part of them are reaching psychosocial stability after they had overcome the cancer disease and its treatment. In the following chapter, we aim to point out social outcomes of survivors and risk factors for adverse outcomes. The latter thus define subgroups for intensified follow-up and care. An early identification of groups at high risk is crucial, in order to understand, and later prevents the pathways leading to poor socioeconomic outcomes. We also provide information how reintegration into everyday life takes place, i.e., which challenges are faced and how they may be overcome.
CRIS-Team Scopus Importer:2024-12-16

Evolutionary conserved networks of human height identify multiple Mendelian causes of short stature - Hauer, Nadine; Popp, Bernt; Taher, Leila; Vogl, Carina; Dhandapany, Perundurai S.; Büttner, Christian; Uebe, Steffen; Sticht, Heinrich; Ferrazzi, Fulvia; Ekici, Arif Bülent; De Luca, Alessandro; Klinger, Patricia; et al. (European journal of human genetics, 2019)
Height is a heritable and highly heterogeneous trait. Short stature affects 3% of the population and in most cases is genetic in origin. After excluding known causes, 67% of affected individuals remain without diagnosis. To identify novel candidate genes for short stature, we performed exome sequencing in 254 unrelated families with short stature of unknown cause and identified variants in 63 candidate genes in 92 (36%) independent families. Based on systematic characterization of variants and functional analysis including expression in chondrocytes, we classified 13 genes as strong candidates. Whereas variants in at least two families were detected for all 13 candidates, two genes had variants in 6 (UBR4) and 8 (LAMA5) families, respectively. To facilitate their characterization, we established a clustered network of 1025 known growth and short stature genes, which yielded 29 significantly enriched clusters, including skeletal system development, appendage development, metabolic processes, and ciliopathy. Eleven of the candidate genes mapped to 21 of these clusters, including CPZ, EDEM3, FBRS, IFT81, KCND1, PLXNA3, RASA3, SLC7A8, UBR4, USP45, and ZFHX3. Fifty additional growth-related candidates we identified await confirmation in other affected families. Our study identifies Mendelian forms of growth retardation as an important component of idiopathic short stature.
CRIS-Team Scopus Importer:2019-05-24

Evolving pituitary hormone deficits in primarily isolated GHD: a review and experts' consensus. - Binder, Gerhard; Schnabel, Dirk; Reinehr, Thomas; Pfaeffle, Roland; Dörr, Helmuth-Günther; Bettendorf, Markus; Hauffa, Berthold P.; Wölfle, Joachim (Molecular and Cellular Pediatrics, 2020)
Isolated growth hormone deficiency (GHD) is defined by growth failure in combination with retarded bone age, low serum insulin-like growth factor-1, and insufficient GH peaks in two independent GH stimulation tests. Congenital GHD can present at any age and can be associated with significant malformations of the pituitary-hypothalamic region or the midline of the brain. In rare instances, genetic analysis reveals germline mutations of transcription factors involved in embryogenesis of the pituitary gland and the hypothalamus. Acquired GHD is caused by radiation, inflammation, or tumor growth. In contrast to organic GHD, idiopathic forms are more frequent and remain unexplained.There is a risk of progression from isolated GHD to combined pituitary hormone deficiency (> 5% for the total group), which is clearly increased in children with organic GHD, especially with significant malformation of the pituitary gland. Therefore, it is prudent to exclude additional pituitary hormone deficiencies in the follow-up of children with isolated GHD by clinical and radiological observations and endocrine baseline tests. In contrast to primary disorders of endocrine glands, secondary deficiency is frequently milder in its clinical manifestation. The pituitary hormone deficiencies can develop over time from mild insufficiency to severe deficiency. This review summarizes the current knowledge on diagnostics and therapy of additional pituitary hormone deficits occurring during rhGH treatment in children initially diagnosed with isolated GHD. Although risk factors are known, there are no absolute criteria enabling exclusion of children without any risk of progress to combined pituitary hormone deficiency. Lifelong monitoring of the endocrine function of the pituitary gland is recommended in humans with organic GHD. This paper is the essence of a workshop of pediatric endocrinologists who screened the literature for evidence with respect to evolving pituitary deficits in initially isolated GHD, their diagnosis and treatment.
EVALuna2:385043
Keywords: Isolated GHD; Combined pituitary hormone deficiency; Organic GHD; Pituitary gland malformation; Acquired GHD

Exploring the phenotypical spectrum of BRD4 defects - Hauer, Nadine; Vogl, C.; Popp, Bernt; Buettner, C.; Uebe, S.; Sticht, Heinrich; Ekici, Arif Bülent; Klinger, Patricia; Kraus, Cornelia; Krumbiegel, M.; Wiesener, A.; Dörr, Helmuth-Günther; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2019)
CRIS-Team WoS Importer:2019-10-25

First-year predictors of health-related quality of life changes in short-statured children treated with human growth hormone - Quitmann, J.; Bloemeke, J.; Dörr, Helmuth-Günther; Bullinger, M.; Witt, S.; Silva, N. (Journal of Endocrinological Investigation, 2019)
Purpose: Little attention has been directed towards examining the impact of predictors on change in health-related quality of life (HRQOL) within the course of growth hormone (GH) treatment in pediatric short stature. We aimed to assess changes in HRQOL and its sociodemographic, clinical and psychosocial predictors in children and adolescents diagnosed with growth hormone deficiency (GHD), and born short for gestational age (SGA) before and 12-month after start of GH treatment from the parents’ perspective. Results were compared with an untreated group with idiopathic short stature (ISS). In this prospective multicenter study, 152 parents of children/adolescents (aged 4–18 years) provided data on their children’s HRQOL at baseline and at 12-month follow-up. Method: Repeated-measures multivariate analyses of covariance were performed to examine parent-reported HRQOL changes from baseline to 1-year after treatment and hierarchical linear regressions to identify the predictors of HRQOL changes. Results: Results showed that parents of children that were treated with GH report an increase in their children’s HRQOL after 1 year. Changes in HRQOL were mostly explained by psychosocial predictors followed by sociodemographic and clinical variables. Specifically, the diagnosis SGA significantly predicted a greater increase in parent-reported HRQOL. Furthermore, a lower caregiving burden significantly predicted a decrease in parent-reported HRQOL. Conclusion: In conclusion, a substantial percentage of explained variance in HRQOL relates to psychosocial and sociodemographic predictors. However, there appears to be other important factors that are predictors of HRQOL, which need to be determined in large, population-based samples.
CRIS-Team Scopus Importer:2019-08-23
Keywords: Children and adolescents; Growth hormone treatment; HRQOL; Predictors of change; Short stature

Genetic screening confirms heterozygous mutations in ACAN as a major cause of idiopathic short stature - Hauer, Nadine; Sticht, Heinrich; Boppudi, Sangamitra; Büttner, Christian; Kraus, Cornelia; Trautmann, Udo; Zenker, Martin; Zweier, Christiane; Wiesener, Antje; Abou Jamra, Rami; Wieczorek, Dagmar; Kelkel, Jaqueline; et al. (Scientific Reports, 2017)
Short stature is a common pediatric disorder affecting 3% of the population. However, the clinical variability and genetic heterogeneity prevents the identification of the underlying cause in about 80% of the patients. Recently, heterozygous mutations in the ACAN gene coding for the proteoglycan aggrecan, a main component of the cartilage matrix, were associated with idiopathic short stature. To ascertain the prevalence of ACAN mutations and broaden the phenotypic spectrum in patients with idiopathic short stature we performed sequence analyses in 428 families. We identified heterozygous nonsense mutations in four and potentially disease-causing missense variants in two families (1.4%). These patients presented with a mean of -3.2 SDS and some suggestive clinical characteristics. The results suggest heterozygous mutations in ACAN as a common cause of isolated as well as inherited idiopathic short stature.
EVALuna2:9379

GENETICS IN ENDOCRINOLOGY: Gain and loss of function mutations of the calcium-sensing receptor and associated proteins: current treatment concepts - Mayr, Bernhard; Schnabel, Dirk; Dörr, Helmuth-Günther; Schöfl, Christof (European Journal of Endocrinology, 2016)
The calcium-sensing receptor (CASR) is the main calcium sensor in the maintenance of calcium metabolism. Mutations of the CASR, the G protein alpha 11 (GNA11) and the adaptor-related protein complex 2 sigma 1 subunit (AP2S1) genes can shift the set point for calcium sensing causing hyper- or hypo-calcemic disorders. Therapeutic concepts for these rare diseases range from general therapies of hyper- and hypo-calcemic conditions to more pathophysiology oriented approaches such as parathyroid hormone (PTH) substitution and allosteric CASR modulators. Cinacalcet is a calcimimetic that enhances receptor function and has gained approval for the treatment of hyperparathyroidism. Calcilytics in turn attenuate CASR activity and are currently under investigation for the treatment of various diseases. We conducted a literature search for reports about treatment of patients harboring inactivating or activating CASR, GNA11 or AP2S1 mutants and about in vitro effects of allosteric CASR modulators on mutated CASR. The therapeutic concepts for patients with familial hypocalciuric hypercalcemia (FHH), neonatal hyperparathyroidism (NHPT), neonatal severe hyperparathyroidism (NSHPT) and autosomal dominant hypocalcemia (ADH) are reviewed. FHH is usually benign, but symptomatic patients benefit from cinacalcet. In NSHPT patients pamidronate effectively lowers serum calcium, but most patients require parathyroidectomy. In some patients cinacalcet can obviate the need for surgery, particularly in heterozygous NHPT. Symptomatic ADH patients respond to vitamin D and calcium supplementation but this may increase calciuria and renal complications. PTH treatment can reduce relative hypercalciuria. None of the currently available therapies for ADH, however, prevent tissue calcifications and complications, which may become possible with calcilytics that correct the underlying pathophysiologic defect.
EVALuna2:2068

Genotype/phenotype correlations in 538 congenital adrenal hyperplasia patients from Germany and Austria: discordances in milder genotypes and in screened versus prescreening patients - Riedl, Stefan; Roehl, Friedrich-Wilhelm; Bonfig, Walter; Braemswig, Juergen; Richter-Unruh, Annette; Fricke-Otto, Susanne; Bettendorf, Markus; Riepe, Felix; Kriegshaeuser, Gernot; Schoenau, Eckhard; Even, Gertrud; Hauffa, Berthold; et al. (Endocrine Connections, 2019)
Congenital adrenal hyperplasia (CAH) due to CYP21A2 gene mutations is associated with a variety of clinical phenotypes (salt wasting, SW; simple virilizing, SV; nonclassical, NC) depending on residual 21-hydroxylase activity. Phenotypes and genotypes correlate well in 80-90% of cases. We set out to test the predictive value of CAH phenotype assignment based on genotype classification in a large multicenter cohort. A retrospective evaluation of genetic data from 538 CAH patients (195 screened) collected from 28 tertiary centers as part of a German quality control program was performed. Genotypes were classified according to residual 21-hydroxylase activity (null, A, B, C) and assigned clinical phenotypes correlated with predicted phenotypes, including analysis of Prader stages. Ultimately, concordance of genotypes with clinical phenotypes was compared in patients diagnosed before or after the introduction of nationwide CAH-newborn screening. Severe genotypes (null and A) correlated well with the expected phenotype (SW in 97 and 91%, respectively), whereas less severe genotypes (B and C) correlated poorly (SV in 45% and NC in 57%, respectively). This was underlined by a high degree of virilization in girls with C genotypes (Prader stage >1 in 28%). SW was diagnosed in 90% of screening-positive babies with classical CAH compared with 74% of prescreening patients. In our CAH series, assigned phenotypes were more severe than expected in milder genotypes and in screened vs prescreening patients. Diagnostic discrimination between phenotypes based on genotypes may prove overcome due to the overlap in their clinical presentations.
CRIS-Team WoS Importer:2019-03-20

Genotype-phenotype correlations in children and adolescents with nonclassical congenital adrenal hyperplasia due to 21-hydroxylase deficiency. - Dörr, Helmuth-Günther; Schulze, Nadja; Bettendorf, Markus; Binder, Gerhard; Bonfig, Walter; Denzer, Christian; Dunstheimer, Desirée; Salzgeber, Kirsten; Schmidt, Heinrich; Schwab, Karl-Otfried; Voss, Egbert; Wabitsch, Martin; et al. (Molecular and Cellular Pediatrics, 2020)
BACKGROUND: Nonclassical congenital adrenal hyperplasia due to 21-hydroxylase deficiency is caused by mutations in the active 21-hydroxylase gene (CYP21A2). The clinical symptoms can vary greatly. To date, no systematic studies have been undertaken in Germany. AIMS: Description of the phenotype, evaluation of the diagnostics and genotype-phenotype correlation PATIENTS AND METHODOLOGY: Retrospective analysis of the data of 134 patients (age range 0.1-18.6 years) in a multicentre study covering 10 paediatric endocrinology centres in Bavaria and Baden-Württemberg. The data was gathered on site from the medical records. Two hundred and thirty-three alleles with a mutation of the CYP21A2 gene were identified in 126 patients. A genotype-phenotype correlation of the mutation findings was undertaken (C1, severe/mild; C2, mild/mild). Individuals with a heterozygous mutation of the CYP21A2 were also included (C3). The data was collected with the approval of the ethics committee of the University Hospital of Erlangen during the period of 2014 and 2015. RESULTS (MW ± SD): One hundred and seventeen out of 134 patients (115 f, 29 m) were symptomatic. The chronological age (CA) at diagnosis was 7.1 ± 4.4 years. The most frequent symptom (73.5%) was premature pubarche. The height-SDS on diagnosis was 0.8 ± 1.3 and the BMI-SDS was 0.8 ± 1.2. Bone age (BA) was ascertained in 82.9% of the symptomatic patients. The difference between BA and CA was 1.9 ± 1.4 years. Basal 17OHP concentrations were 14.5 ± 19.1 ng/ml (18 patients < 2 ng/ml). In total, 58.1% mild and 34.7% severe mutations were found. The most common mutation was p.Val281Leu (39.1%); 65.8% of the patients could be allocated to group C1. No phenotypical differences were found between the 3 mutation groups. The 17OHP levels (basal and after ACTH) in the standard ACTH stimulation test were highest in group C1 and also significantly higher in group C2 as in C3, the ACTH-stimulated cortisol levels (ng/ml) were significantly lower in groups C1 (192.1 ± 62.5) and C2 (218 ± 50) than in C3 (297.3 ± 98.7). CONCLUSION: Most of the patients have symptoms of mild androgenisation. Male patients are underdiagnosed. Diagnostics are not standardised. Differences between the types of mutations are found in the hormone concentrations but not in phenotype. We speculate that further, as yet not clearly defined, factors are responsible for the development of the respective phenotypes.
EVALuna2:385044

Genotyp-Phänotyp-Korrelation bei Zwillingsmädchen mit nichtklassischem adrenogenitalem Syndrom und 21-Hydroxylase-Defekt - Dörr, Helmuth-Günther; Oppelt, Patricia (Gynakologische Endokrinologie, 2020)
CRIS-Team Scopus Importer:2020-03-06

Genotyp-Phänotyp-Korrelationen bei Kindern und Jugendlichen mit nichtklassischem adrenogenitalen Syndrom mit 21-Hydroxylase-Defekt - Dörr, Helmuth-Günther; Schulze, Nadja; Bettendorf, M.; Binder, G.; Bonfig, W.; Denzer, C.; Dunstheimer, D.; Salzgeber, K.; Schmidt, H.; Schwab, K. O.; Voss, E.; Wabitsch, M.; et al. (Monatsschrift Kinderheilkunde, 2020)
Background: Nonclassical congenital adrenal hyperplasia due to 21-hydroxylase deficiency (NCCAH) is caused by mutations in the active 21-hydroxylase gene (CYP21A2). The clinical symptoms can vary greatly. To date, no systematic studies have been undertaken in Germany. Objective: Description of the phenotype, evaluation of the diagnostics, genotype-phenotype correlation. Patients and methodology: Retrospective analysis of the data of 134 patients (age range 0.1–18.6 years) in a multicenter study covering 10 pediatric endocrinology centers in Bavaria and Baden-Württemberg. The data were collected on site from the medical records. In 126 patients 233 alleles with a mutation of the CYP21A2 gene were identified. A genotype-phenotype correlation of the mutation findings was undertaken (C1: severe/mild, C2: mild/mild). Individuals with a heterozygote mutation (C3) were also included in the analysis. The data were collected with the approval of the ethics committee of the University Hospital of Erlangen during the time period of 2014 and 2015. Results (MW ± SD): Out of 134 patients (115 female, 29 male) 117 were symptomatic. The chronological age (CA) at diagnosis was 7.1 ± 4.4 years. The most frequent symptom (73.5%) was premature pubarche. The height-standard deviation score (SDS) on diagnosis was 0.8 ± 1.3 and the body mass index (BMI)-SDS was 0.8 ± 1.2. Bone age (BA) was ascertained in 82.9% of the symptomatic patients. The difference between BA and CA was 1.9 ± 1.4 years. Basal 17-hydroxyprogesterone (17-OHP) concentrations were 14.5 ± 19.1 ng/ml (18 patients <2 ng/ml). In total 58.1% mild and 34.7% severe mutations were found. The most common mutation (39.1%) was p.Val281Leu and 65.8% of the patients could be allocated to group C1. No phenotypical differences were found between the three mutation groups. The 17-OHP levels (basal and after ACTH) in the ACTH test were highest in group C1 and also significantly higher in group C2 than in group C3. The ACTH-stimulated cortisol levels (ng/ml) were significantly lower in groups C1 (192.1 ± 62.5) and C2 (218 ± 50) than in C3 (297.3 ± 98.7). Conclusion: Most of the patients had symptoms of mild androgenization. Male patients were underdiagnosed. The diagnostics were not standardized. Differences between the types of mutations were found in the hormone concentrations but not in the phenotype. We speculate that further, as yet not clearly defined, factors are responsible for the development of the respective phenotypes.
CRIS-Team Scopus Importer:2020-07-24
Keywords: 17-OHP; ACTH stimulation test; Androgenisation; CYP21A2 gene mutations; Premature pubarche

Glukokortikoide bei nichtendokrinen Erkrankungen, bei Kortisolmangel und bei endogenem Exzess – der Einfluss therapeutischer Strategien auf das kindliche Wachstum - Hauffa, B. P.; Binder, G.; Bonfig, W.; Bettendorf, M.; Dörr, Helmuth-Günther (Monatsschrift Kinderheilkunde, 2019)
Background: Adrenocortical hormones can influence the growth of children and adolescents. Objective: How does chronic glucocorticoid treatment of nonendocrine diseases and endogenous Cushing’s syndrome affect growth? What has to be considered during the treatment of patients with central adrenal cortex insufficiency under growth hormone substitution and patients with congenital adrenal hyperplasia with respect to growth? Material and methods: This article is based on the results of a workshop held by pediatric endocrinologists. Each author conducted a recent literature research on growth under the specific aspects of adrenal cortex physiology and pathology and the respective treatment procedures. Results: The therapeutic use of high doses of synthetic glucocorticoids for nonendocrine disorders (pharmacological treatment) inhibits the growth of children and adolescents. Long-term use should therefore be avoided and glucocorticoid-sparing treatment regimens (biologicals etc.) should be preferred. High endogenous cortisol levels in Cushing’s syndrome cause growth retardation; however, if the secretion of androgens predominates, longitudinal growth can also be increased. In patients with growth hormone deficiency, the possibility of a delayed failure of the hypothalamus-pituitary-adrenal cortex axis has to be considered and a re-evaluation should be scheduled. High doses of hydrocortisone during substitution should be avoided so as not to compromise the effect of the growth hormone therapy (substitution therapy). Patients with congenital adrenal hyperplasia and 21-hydroxylase deficiency show specific growth characteristics in the different phases of life. It is therefore a therapeutic challenge to achieve a normal final body height by individually adapting glucocorticoid treatment. Conclusion: The adequate diagnosis, treatment and monitoring of disorders of adrenal cortex function are important to minimize the negative effects on the growth of children and adolescents.
CRIS-Team Scopus Importer:2019-06-07
Keywords: Adrenal glands; Congenital adrenal hyperplasia; Cushing’s syndrome; Hydrokortisone; Synthetic Glucocorticoids

Graves’ disease in children with Down syndrome - Cebeci, Ayse Nurcan; Schempp, Vera; Förtsch, Katharina; Gohlke, Bettina; Marx, Martin; Dörr, Helmuth-Günther; Wölfle, Joachim (Endocrine Connections, 2024)
While subclinical or overt hypothyroidism are common in Down syndrome (DS); Graves’ disease (GD) is rare (ranges 0.6–3%). We aimed to evaluate the clinical features, course, and treatment of GD in children with DS and compare them with those without DS. Among 161 children with GD, 13 (8 female, 5 male) had DS (8%). Data were collected retrospectively from patients’ medical records. The mean age at diagnosis was 10.6 ± 4.5 years, with a female-to-male ratio 1.6:1. The main symptoms were weight loss (n = 6), increased irritability (n = 3), and increased sweating (n = 3). None had orbitopathy. Seven of 11 patients with a thyroid ultrasound at diagnosis had a goitre. On admission, all had thyroid-stimulating hormone (TSH) <0.01 mU/L (normal range (NR): 0.51–4.30), free triiodothyronine, free thyroxine (mean ± s.d.), and thyrotrophin receptor antibodies (median, range) were 22.2 ± 10.2 pmol/L (NR: 3.5–8.1), 50.2 ± 18.7 pmol/L (NR 12.6–20.9), and 17.0 (2.89–159.0) U/L (NR <1), respectively. Patients were treated either with methimazole (n = 10) or carbimazole (n = 3), a dose of 0.54 ± 0.36 mg/kg/day. The treatment was ‘block and replace’ in ten patients and ‘dose titration’ in three patients, with a mean duration of 43.4 ± 11.0 months. Of 13 patients, four are still receiving primary treatment, three are in remission, one patient had two medically treated recurrences, three underwent surgery without complications, and two patients were lost to follow-up. Our data show that the clinical course of GD in patients with DS was similar to those without DS and suggest that a prolonged medical therapy should be the preferred option.
CRIS-Team Scopus Importer:2024-06-28
Keywords: anti-thyroid drug medication; autoimmune thyroiditis; Down syndrome; Graves’ disease; hyperthyroidism

Größenwachstum und Knochengesundheit bei Erkrankungen der Wachstumsfuge und des Knochens: Möglichkeiten und Grenzen einer GH-Therapie - Wölfle, Joachim; Bettendorf, M.; Bechtold-Dalla Pozza, S.; Binder, G.; Grasemann, C.; Reinehr, T.; Semler, O.; Dörr, Helmuth-Günther (Monatsschrift Kinderheilkunde, 2020)
Background: Genetic, paracrine and endocrine factors influence longitudinal growth in the area of the epiphyseal plates and bone mineralization. Objective: The aim was to review the spontaneous longitudinal growth and bone health in patients with rare bone diseases. Can growth hormone (GH) treatment improve growth and bone health in these diseases? Material and methods: Findings of an expert workshop including literature search on bone health in bone disorders associated with stunted growth and the treatment options. Results: Most patients with osteogenesis imperfecta are of short stature. Additional administration of GH has no influence on adult height and is currently not used. Pseudohypoparathyroidism (PHP) patients with insufficient longitudinal growth and confirmed GH deficiency can be treated with GH and can benefit from the treatment. Children with X‑linked hereditary hypophosphatemic rickets show progressive disproportionate short stature under the current treatment with phosphate and calcitriol. Randomized GH treatment studies resulted in a temporary improvement in body height but not in a significant improvement of adult height. The use of GH is approved for treatment of SHOX-deficient children and is comparably effective as in girls with Turner’s syndrome (TS). Observational studies also suggest that GH treatment can lower the risk of bone fractures, known to be increased in TS. Inflammation, reduced physical activity and malnutrition can result in impaired growth with loss of muscle and bone mass in patients with juvenile idiopathic arthritis (JIA). Studies could demonstrate a positive impact of GH on longitudinal growth, density and geometry of bones and on bone metabolism as well as on muscular mass; however, GH treatment is not approved for patients with JIA. Conclusion: Regarding the various bone diseases mentioned above, all growth disorders have to be considered individually. Apart from longitudinal growth GH can have a positive impact on metabolism, bone mineral content and bone density depending on the indications. The only approved indications for GH treatment are GH deficiency in PHP and children born small for gestational age (SGA) and TS/SHOX deficiency. Apart from increased growth, improvements in bone health in children and adolescents should be discussed as an outcome measure for GH treatment.
CRIS-Team Scopus Importer:2020-10-02
Keywords: Bone; Bone health; Growth; Growth hormone (GH); Growth plate

Growth hormone treatment in children with short stature: impact of the diagnosis on parents - Witt, Stefanie; Bloemeke, Janika; Bullinger, Monika; Dörr, Helmuth-Günther; Silva, Neuza; Quitmann, Julia Hannah (Journal of Pediatric Endocrinology & Metabolism, 2024)
Objectives: This prospective multicenter study aimed (1) to examine changes in parent-reported health-related quality of life (HRQOL) of children with short stature and the effects of the children’s condition on parents themselves within the first year of human growth hormone (hGH) treatment and (2) to predict effects on parents based on main and interaction effects of children’s HRQOL and increase in height. Methods: A total of 110 parents of children aged 4–18 years, diagnosed with idiopathic growth hormone deficiency, small for gestational age, or idiopathic short stature, were recruited from 11 participating German pediatric endocrinologists and asked to fill out the short stature-specific Quality of Life in Short Stature Youth (QoLISSY) Questionnaire before hGH treatment was initiated and one year later. Results: Negative effects of the children’s short stature on the parents decrease over time, independent of diagnosis and treatment status. Furthermore, treatment status and height increase moderated the links between children’s improved HRQOL as perceived by their parents and decreased caregiving burden. Conclusions: Based on the children’s improved HRQOL and the parent’s decrease in caregiving burden, patient-reported outcomes that consider parental and child’s perspectives should be considered when deciding on hGH treatment for children.
CRIS-Team Scopus Importer:2024-04-26
Keywords: health-related quality of life; human growth hormone treatment; parental burden; short-statured children

Growth in disorders and normal variants of puberty - Binder, G.; Bettendorf, M.; Dörr, Helmuth-Günther; Hauffa, B. P.; Reinehr, T.; Richter-Unruh, A.; Rohrer, T. R.; Woelfle, J. (Monatsschrift Kinderheilkunde, 2019)
BackgroundDisorders of puberty may affect growth.ObjectiveHow do precocious puberty, constitutional delay of growth and puberty (CDGP) and hypogonadism impact parameters of growth, such as growth velocity, bone maturation and adult height and when is treatment required?Material and methodsThis article is based on the results of a working party meeting of pediatric endocrinologists. Each author carried out areview of the current literature about growth in the context of disorders of pubertal development and the respective treatment.ResultsIf untreated precocious puberty almost always results in short stature in adulthood. Affected children can achieve an individual adult target height if treatment with gonadotropin-releasing hormone (GnRH) analogues is started early. The CDGP is aslow variant of childhood growth rate with normal unaffected adult height and treatment is not necessary. Overweight can be associated with an acceleration of growth and pubertal maturity but adult height is also unaffected. Children with hypogonadism usually reach normal adult height after pharmaceutical induction of puberty. Complex hypothalamic and hypopituitary disorders (hypogonadism plus deficiency of growth hormones), e.g. that can occur after cancer treatment in childhood, need early diagnosis and individualized therapy to preserve the growth potential of the patient.ConclusionEarly diagnosis and adequate therapy of disorders of puberty are the cornerstones for an optimal growth outcome of affected children.
CRIS-Team WoS Importer:2019-03-22

Growth in thyroid disorders in childhood and adolescence. Thyroid dysfunction and growth - Bettendorf, M.; Binder, G.; Hauffa, B. P.; Pohlenz, J.; Rohrer, T. R.; Schöfl, Christof; Dörr, Helmuth-Günther (Monatsschrift Kinderheilkunde, 2016)
Disorders of the thyroid function of mother and child can not only irreversibly inhibit maturation of the central nervous system, but may also affect growth and puberty. Review of the consequences of thyroid function disorders on the growth of children and adolescents and the relevance of adequate treatment. This article summarises the current literature concerning the effect of thyroid hormone disorders of mother and child and their therapy on growth. Every untreated manifestation of congenital or acquired hypothyroidism is associated with a delay of growth and skeletal maturation. In children presenting with acquired hyperthyroidism, height is shifted towards higher values and skeletal maturation is accelerated. Approximately 20 % of children and adolescents with Down syndrome develop primary hypothyroidism, frequently manifesting within the first months of life (approximately 5.5 %). Adequate treatment of the thyroid disorder can normalise growth disorders. About 6 % of children with growth hormone deficiency develop abnormally low free thyroxin (fT4) levels in serum during growth hormone treatment due to increased conversion of T4 to T3. There is no indication for treatment after excluding secondary hypothyroidism. Early diagnosis and timely, adequate treatment of thyroid function disorders of mother and child are essential to achieving growth that is as age-appropriate as possible in affected children and adolescents.
EVALuna2:33874

Hydrocortisone dosing in children with classic congenital adrenal hyperplasia: Results of the german/austrian registry - Hoyer-Kuhn, Heike; Huebner, Angela; Richter-Unruh, Anette; Bettendorf, Markus; Rohrer, Tilman; Kapelari, Klaus; Riedl, Stefan; Mohnike, Klaus; Dörr, Helmuth-Günther; Roehl, Friedrich Wilhelm; Fink, Katharina; Holl, Reinhard W.; et al. (Endocrine Connections, 2021)
Objective: Treatment of classic congenital adrenal hyperplasia (CAH) is necessary to compensate for glucocorticoid/mineralocorticoid deficiencies and to suppress androgen excess. Hydrocortisone (HC) is preferred in growing children with classic CAH but recommendations regarding dosage/administration are inconsistent. The aim of this study was to evaluate HC dosing in children with CAH in relation to chronological age, sex, and phenotype based on a multicenter CAH registry. Design: The CAH registry was initiated in 1997 by the AQUAPE in Germany. On December 31st 2018, data from 1571 patients were included. Methods: A custom-made electronic health record software is used at the participating centers. Pseudonymized data are transferred for central analysis. Parameters were selected based on current guidelines. Descriptive analyses and linear regression models were implemented with SAS 9.4. Results: We identified 1288 patients on exclusive treatment with hydrocortisone three times daily (604 boys; median age 7.2 years; 817 salt-wasting phenotype, 471 simple-virilizing phenotype). The mean (lower-upper quartiles) daily HC dose (mg/m² body surface area) was 19.4 (18.9–19.8) for patients <3 months (n = 329), 15.0 (14.6–15.3) for age ≥3–12 months (n = 463), 14.0 (13.7–14.3) for age 1–5.9 years (n = 745), 14.2 (14.0–14.5) for age 6 years to puberty entry (n = 669), and 14.9 (14.6–15.2) during puberty to 18 years (n = 801). Fludrocortisone was administered in 74.1% of patients with a median daily dosage of 88.8 µg. Conclusion: Our analyses showed that still a high proportion of children are treated with HC doses higher than recommended. This evaluation provides comprehensive information on nationwide hydrocortisone substitution dosages in children with CAH underlining the benefit of systematic data within a registry to assess daily practice.
CRIS-Team Scopus Importer:2021-06-11
Keywords: CYP21A2; fludrocortisone; glucocorticoids; treatment

Identification of novel candidate genes for idiopathic short stature using whole exome sequencing - Thiel, Christian; Hauer, Nadine; Vogl, C.; Ahmadian, R.; Dhandapany, P. S.; Popp, Bernt; Buettner, C.; Ube, S.; Sticht, Heinrich; Ferrazzi, Fulvia; Ekici, Arif Bülent; De Luca, A.; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2019)
CRIS-Team WoS Importer:2019-10-25

Impact of Newborn Screening on Adult Height in Patients With Congenital Adrenal Hyperplasia (CAH) - Hoyer-Kuhn, Heike; Eckert, Alexander J.; Binder, Gerhard; Bonfig, Walter; Dübbers, Angelika; Riedl, Stefan; Wölfle, Joachim; Dörr, Helmuth-Günther; Holl, Reinhard W. (Journal of Clinical Endocrinology and Metabolism, 2023)
CONTEXT: Treatment of children with classical congenital adrenal hyperplasia (CAH) due to 21-hydroxylase deficiency is challenging. Linear growth and adult height are compromised according to recent publications. However, most of these data were obtained in the era before CAH newborn screening. DESIGN: Body height of patients with classical CAH diagnosed before and after the establishment of newborn screening were analyzed retrospectively. PATIENTS AND METHODS: We identified 600 patients with classical CAH (227 male) with data on near-adult height (NAH), target height (TH), and information on newborn screening from the electronic German CAH registry (German Society for Paediatric Endocrinology and Diabetology). Newborn screening was performed in 101 (16.8%) patients. All patients received hydrocortisone with or without fludrocortisone.To assess the effects of newborn screening, a linear regression model adjusted/stratified for sex and phenotype was used (SAS 9.4). RESULTS: TH corrected NAH (mean; 95% confidence interval) was closer to 0 in patients with CAH and newborn screening [-0.25 standard deviation score (SDS); -0.44 to -0.06] than in patients without newborn screening (-0.44 SDS; -0.52 to -0.36) (P = .069). Screening had no effect on NAH in female patients. In male patients, NAH was significantly better (P = .033) with screening than without screening. After stratifying for CAH phenotype, screening did not affect the NAH of patients with salt-wasting CAH. Patients with simple-virilizing CAH had a significantly better cNAH (P = .034) with screening (0.15 SDS; -0.28-0.59) than without screening (-0.35 SDS; -0.52 to -0.18). CONCLUSIONS: Our data suggest that newborn screening might be associated with improved NAH in male CAH patients and in patients with simple-virilizing CAH.
CRIS-Team Scopus Importer:2023-11-03
Keywords: congenital adrenal hyperplasia; CYP21A2; near adult height; newborn screening

Intrauterine Growth Restriction (IUGR) Induces Signs of Subclinical Atherosclerosis in 6-Year-Old Infants Despite Absence Of Excessive Growth - Tzschoppe, Anja; Von Kries, Ruediger; Struwe, Ellen; Rascher, Wolfgang; Dörr, Helmuth-Günther; Juengert, Joerg; Rauh, Manfred; Beckmann, Matthias; Schild, Ralf; Goecke, Tamme W.; Doetsch, Joerg (Klinische Pädiatrie, 2017)
Background Postnatal catch-up growth and rapid weight gain after intrauterine growth restriction (IUGR) seem to increase the risk for later disease. This study aimed to compare features of the metabolic syndrome early in life between IUGR and appropriate for gestational age (AGA) infants. Patients Data for 9 infants with IUGR defined by a birth weight<10th percentile and ultrasound-proven placental insufficiency and 11 AGA children were available. Method Postnatal growth, auxological, cardiovascular, and metabolic parameters up to a chronological age of 6 years were assessed: Fasting serum concentrations of LDL-cholesterol, insulin, leptin, IGF-I, DHEAS, skinfold thicknesses, blood pressure, and mean carotid intima-media thickness (cIMT). Results All IUGR infants showed catch-up growth, although mean BMI SDS and total subcutaneous fat mass at the age of 6 years were still slightly lower compared to the AGA cohort. Reduced serum leptin concentrations were observed in IUGR infants (p=0.02), whereas no significant difference was found for IGF-I, insulin, LDL-cholesterol and DHEAS concentrations. Mean cIMT was significantly higher in IUGR infants (p<0.05). Mean arterial pressure did no differ. Discussion and Conclusion In 6-year-old IUGR infants with catch-up growth, who still had a slightly reduced BMI SDS compared to the AGA group, signs of subclinical atherosclerosis were detectable suggesting that cardiovascular risk in IUGR may be present even in the absence of excessive growth.
EVALuna2:34095

Lang wirksames Wachstumshormon – eine neue Therapieoption für Kinder mit Wachstumshormonmangel: Status 2024 - Dörr, Helmuth-Günther; Bettendorf, Markus; Wölfle, Joachim; Saenger, Paul; Ranke, Michael B. (Monatsschrift Kinderheilkunde, 2024)
Until recently, daily singular subcutaneous injections of recombinant human growth hormone (rhGH) was the treatment of choice in short-statured children with growth hormone deficiency (GHD). This concept has been effective and safe for almost four decades; however, with this practice of replacement therapy approximately 10–20% of the children did not reach an adult height within the target range of the parents. Among the various factors involved, insufficient adherence, as the consequence of the necessary but inconvenient daily injections has been identified as a particularly important factor. This prompted the development of long-acting growth hormone (LAGH). At the end of 2023 there were three approved LAGH preparations available in Germany for the treatment of children older than 3 years with GHD due to an insufficient secretion of GH. All approved LAGH formulations use different technologies to prolong the half-life of rhGH. The LAGH as well as rhGH bind to the GH receptor and initiate the signal cascade that leads to the activation of growth and metabolism. In phase 3 studies LAGH showed non-inferiority to daily rhGH injections in terms of increasing height as well as comparability in the safety profiles. Thus, the treatment with LAGH offers a new option for children and adolescents with GHD; however, the long-term efficacy and safety need further systematic evaluation. Parents and patients need to be informed about all relevant aspects of the new treatment. This review article discusses the currently approved LAGH preparations in Germany together with the published data from a pediatric perspective.
CRIS-Team Scopus Importer:2024-08-16
Keywords: Adherence; Lonapegsomatropin; Somapacitan; Somatrogon

Lebensqualität von kleinwüchsigen Kindern und Jugendlichen und Wachstumshormontherapie - Quitmann, Julia Hannah; Binder, Gerhard; Witt, Stefanie; Bullinger, Monika; Blömeke, Janika; Fricke-Otto, Susanne; Hauffa, Berthold; Kahrs, Sabine; Partsch, Carl Joachim; Rohenkohl, Anja; Dörr, Helmuth-Günther (Monatsschrift Kinderheilkunde, 2024)
Background: Pediatric growth disorders can have psychosocial and physical consequences for affected children, adolescents and their families. Objective: How do growth disorders and their treatment with growth hormones (human growth hormone; hGH) affect the quality of life of children and adolescents in the context of idiopathic growth hormone deficiency (IGHD), idiopathic short stature (ISS), Turner syndrome (TS), small for gestational-age (SGA) short stature, and Prader-Willi syndrome (PWS) and their parents? Material and methods: Results of a multiprofessional working meeting with a current literature review. Results: In Germany hGH treatment is not indicated for all mentioned diagnoses. The quality of life of children and adolescents with growth disorders and their parents is often impaired but not necessarily. For example, children and adolescents with ISS often report an average or even higher quality of life than normal growth peers. Similarly, children with PWS also report comparable quality of life to peers. Children with IGHD report impaired quality of life, and girls with TS also report adverse effects on their self-esteem and social life due to their physical health. The associations of hGH treatment and quality of life show inconsistent results; thus, studies report both unchanged quality of life (TS, IGHD) and improved quality of life (IGHD, SGA, PWS). Conclusion: Pediatric growth disorders partly have psychosocial and physical consequences but studies show inconsistent research results. Other factors besides body height play an essential role in assessing the quality of life, such as coping with the disorder.
CRIS-Team Scopus Importer:2024-07-19
Keywords: Child’s wellbeing; Parental burden; Psychosocial consequences; Treatment burden

Lebenssituation von jungen Frauen mit Ullrich-Turner-Syndrom nach dem Ende der Wachstumshormontherapie: Ergebnisse einer Umfrage in Deutschland - Dörr, Helmuth-Günther; Bettendorf, Markus; Binder, Gerhard; Brämswig, Jürgen; Hauffa, Berthold P.; Holterhus, Paul Martin; Mohnike, Klaus; Schmidt, Heinrich; Stalla, Günter K.; Wabitsch, Martin; Wölfle, Joachim (Deutsche Medizinische Wochenschrift, 2019)
Introduction Psychosocial problems such as anxious personality, low self-esteem, late separation from home and/or late sexual experience have been described in girls and women with Turner syndrome (TS). Methods The study was performed in 2015 based on a questionnaire that was sent out to 779 women with TS aged 25 years (median). The questionnaire was devised by a French team and used with their permission. In all, 130 questionnaires (16.7%) could be evaluated. The questions from the individual topics were not always completely answered. Results (mean ± SD). 116 women (89.9%) were not married; 52 women (40%) lived in their parents' home. 47.6% had a high-school/technical diploma or university degree. 60 women (46%) had a job; 51 women (39%) had not completed vocational training. Puberty was induced at the age of 14.2± 2.1 years in 78% of the women. 80% of the women received hormone replacement therapy at the time of the questionnaire survey. 66 of 93 women (71%) found that the disease had a negative influence on emotional life. Love life and sexual relationship was the topic mentioned most frequently by 44 women (66.6%). 116 women answered questions on sexuality. Here, 77% had the first French kiss at the age of 16.4± 3.6 years and 62.4% had sexual intercourse for the first time at the age of 19.0±3.4 years. 81% of the women stated that they had a partner relationship for more than 6 months (94 women had a male partner and 5 had a female partner). The question as to the wish to have children was answered in the affirmative by 89 of 124 women (71.8%); 38.2% desired spontaneous pregnancy and 44.9% had considered in vitro fertilization or adoption. Discussion The women's answers show that care needs to be improved. There are deficits in the topics of family, emotional life, relationships, sexuality, fertility and pregnancy. Therefore, the medical team should also include psychologists and social workers.
CRIS-Team Scopus Importer:2019-07-26
Keywords: emotional life; fertility; questionnaire; sexuality

Levothyroxine Treatment of Euthyroid Children with Autoimmune Hashimoto Thyroiditis: Results of a Multicenter, Randomized, Controlled Trial - Dörr, Helmuth-Günther; Bettendorf, Markus; Binder, Gerhard; Karges, Beate; Kneppo, Carolin; Schmidt, Heinrich; Voss, Egbert; Wabitsch, Martin; Doetsch, Joerg (Hormone Research in Paediatrics, 2015)
Levothyroxine (L-T4) treatment of euthyroid children with Hashimoto thyroiditis (HT) is a controversial issue.We conducted a prospective, randomized, controlled clinical trial. Out of 79 identified euthyroid patients, 59 started the study; 25 patients (21 female, 4 male; age: 11.8 ± 2.3 years) received L-T4 at a mean dose of 1.6 µg/kg (SD, 0.8) daily, and 34 (27 female, 7 male; age: 12.6 ± 1.2 years) were not treated. Patients developing subclinical hypothyroidism during follow-up (n = 13) were treated with L-T4 and removed from the observation group. As the main outcome measures, thyroid gland volume (determined by ultrasound) as well as serum levels of TSH, free T4, and antibodies against thyroid peroxidase and thyroglobulin were assessed every 6 months for 36 months.At the start, the mean thyroid volume (standard deviation score, SDS) was 2.5 in the treatment group and 1.6 in the observation group. There was a constant decline in mean thyroid volume (SDS) from 2.13 (month 12) to 1.12 (month 30) in the treated group, with a delta thyroid volume of -1.01 SDS. In the observation group, the mean delta thyroid volume increased to +0.27 SDS. The change of the delta thyroid volume was statistically significantly different between both groups during the 12- and 30-month time points (p < 0.05). L-T4 had no effect on thyroid function and serum thyroid antibodies.L-T4 treatment can decrease the thyroid volume in euthyroid children with HT, but the effect is limited to a definite time period.
EVALuna2:18916

Life Situation of Young women with Turner Syndrome: Results of a Questionnaire-based Study in Germany - Dörr, Helmuth-Günther; Bettendorf, Markus; Binder, Gerhard; Braemswig, Juergen; Hauffa, Berthold P.; Holterhus, Paul-Martin; Mohnike, Klaus; Schmidt, Heinrich; Stalla, Gunter K.; Wabitsch, Martin; Woelfle, Joachim (Deutsche Medizinische Wochenschrift, 2019)
INTRODUCTION: Psychosocial problems such as anxious personality, low self-esteem, late separation from home and/or late sexual experience have been described in girls and women with Turner syndrome (TS). METHODS: The study was performed in 2015 based on a questionnaire that was sent out to 779 women with TS aged 25 years (median). The questionnaire was devised by a French team and used with their permission. In all, 130 questionnaires (16.7 %) could be evaluated. The questions from the individual topics were not always completely answered. RESULTS: (mean ± SD).: 116 women (89.9 %) were not married; 52 women (40 %) lived in their parents' home. 47.6 % had a high-school/technical diploma or university degree. 60 women (46 %) had a job; 51 women (39 %) had not completed vocational training. Puberty was induced at the age of 14.2 ± 2.1 years in 78 % of the women. 80 % of the women received hormone replacement therapy at the time of the questionnaire survey. 66 of 93 women (71 %) found that the disease had a negative influence on emotional life. "Love life and sexual relationship" was the topic mentioned most frequently by 44 women (66.6 %). 116 women answered questions on sexuality. Here, 77 % had the first French kiss at the age of 16.4 ± 3.6 years and 62.4 % had sexual intercourse for the first time at the age of 19.0 ± 3.4 years. 81 % of the women stated that they had a partner relationship for more than 6 months (94 women had a male partner and 5 had a female partner). The question as to the wish to have children was answered in the affirmative by 89 of 124 women (71.8 %); 38.2 % desired spontaneous pregnancy and 44.9 % had considered in vitro fertilization or adoption. DISCUSSION: The women's answers show that care needs to be improved. There are deficits in the topics of family, emotional life, relationships, sexuality, fertility and pregnancy. Therefore, the medical team should also include psychologists and social workers.
EVALuna2:202757

Long-term Surveillance of Children with Congenital Hypothyroidism: Data from the German Registry for Congenital Hypothyroidism (AQUAPE "Hypo Dok") - Ellerbroek, V. L.; Bonfig, W.; Dörr, Helmuth-Günther; Bettendorf, M.; Hauffa, B.; Fricke-Otto, S.; Rohrer, T.; Reschke, F.; Schoenau, E.; Schwab, K. O.; Kapelari, K.; Roehl, F. -W.; et al. (Klinische Pädiatrie, 2015)
The German study group for quality assurance in pediatric endocrinology and the University of Ulm have established a software ("Hypo Dok") for the documentation of longitudinal data of patients with congenital primary hypothyroidism (CH). Aim of this study was to analyse the long-term follow-up of patients with CH and to compare treatment with current guidelines.Anonymised data of 1,080 patients from 46 centres were statistically analysed.Newborn screening result was available at a mean age of 7.3 days. Confirmation of the diagnosis was established at 8.4 days and therapy was started at 11 days. The average screening TSH was 180.0 mIU/L. During the first 3 months mean levothyroxine (LT4) dose was 10.7 µg/kg/day or 186.0 µg/m²/day. Weight-, BMI- and height-SDS did not differ significantly from the normal population. Only 25% of the patients (n=262) underwent formal EQ/IQ-testing. Their average IQ was 98.8 ± 13.2 points.In Germany screening, confirmation and start of treatment of CH are within the recommended time frame of 14 days. Initial LT4-doses are adequate. The auxological longterm outcome of young CH patients is normal. The implementation of standardized IQ testing has to be improved in routine patient care.Longitudinal data of patients with CH was analysed and compared to current guidelines. Confirmation and start of treatment are according to the recommendations. However standardised IQ testing requires improvement.
EVALuna2:18917

Malformationen des Zentralnervensystems - Seltene Ursachen eines organischen Wachstumshormonmangels bei Kindern - Dörr, Helmuth-Günther; Bettendorf, M.; Binder, G.; Hauffa, B.; Mohnike, K.; Mueller, H. L.; Reinehr, T.; Stalla, G. K.; Woelfle, J. (Monatsschrift Kinderheilkunde, 2020)
Background: Growth hormone (GH) deficiency is a rare endocrine disease. Diagnosis using laboratory investigations must be followed by contrast agent-enhanced magnetic resonance imaging of the central nervous system (CNS). Objective: Overview of rare CNS malformations associated with GH deficiency in children and adolescents. Material and methods: This article was prepared based on lectures held within the framework of a workshop of pediatric endocrinologists in Frankfurt/Main in March 2017. During script preparation, the authors came to a consensus regarding the key statements in the present publication. Results: Malformations of the CNS are extremely rare. Among these malformations, pituitary hypoplasia has been most frequently described, followed by the empty sella syndrome and the pituitary stalk interruption syndrome. Ectopic neurohypophysis has been reported in patients with isolated GH deficiency. Septum pellucidum agenesia, corpus callosum defects, ectopic pituitary gland and optic nerve hypoplasia have been found in patients with septo-optic dysplasia. Pharmacological tests of GH secretion revealed markedly lower maximum GH concentrations in patients with CNS anomalies. As a rule, patients with combined CNS anomalies show better response to GH treatment than patients with only a single anomaly. Conclusion: The availability of data on CNS malformations in children with GH deficiency is unsatisfactory. The data from patients under GH treatment should continue to be documented and analyzed on a systematic basis.
CRIS-Team Scopus Importer:2020-03-27
Keywords: Empty sella; Hypoplastic anterior pituitary; Organic growth hormone deficiency; Rare disease; Septo-optic dysplasia

Malformationen des Zentralnervensystems: Seltene Ursachen eines organischen Wachstumshormonmangels bei Kindern - Dörr, Helmuth-Günther; Bettendorf, M.; Binder, G.; Hauffa, B.; Mohnike, K.; Mueller, H. L.; Reinehr, T.; Stalla, G. K.; Woelfle, J. (Padiatrie und Padologie, 2020)
Background Growth hormone (GH) deficiency is a rare endocrine disease. Diagnosis using laboratory investigations must be followed by contrast agent-enhanced magnetic resonance imaging of the central nervous system (CNS). Objective Overview of rare CNS malformations associated with GH deficiency in children and adolescents. Material and methods This article was prepared based on lectures held within the framework of a workshop of pediatric endocrinologists in Frankfurt/Main in March 2017. During script preparation, the authors came to a consensus regarding the key statements in the present publication. Results Malformations of the CNS are extremely rare. Among these malformations, pituitary hypoplasia has been most frequently described, followed by the empty sella syndrome and the pituitary stalk interruption syndrome. Ectopic neurohypophysis has been reported in patients with isolated GH deficiency. Septum pellucidum agenesia, corpus callosum defects, ectopic pituitary gland and optic nerve hypoplasia have been found in patients with septo-optic dysplasia. Pharmacological tests of GH secretion revealed markedly lower maximum GH concentrations in patients with CNS anomalies. As a rule, patients with combined CNS anomalies show better response to GH treatment than patients with only a single anomaly. Conclusion The availability of data on CNS malformations in children with GH deficiency is unsatisfactory. The data from patients under GH treatment should continue to be documented and analyzed on a systematic basis.
CRIS-Team WoS Importer:2020-05-15

MAP4-dependent regulation of microtubule formation affects centrosome, cilia, and golgi architecture as a central mechanism in growth regulation - Zahnleiter, Diana; Hauer, Nadine; Keßler, Kristin; Uebe, Steffen; Sugano, Yuya; Neuhauss, Stephan C. F.; Gießl, Andreas; Ekici, Arif Bülent; Blessing, Holger; Sticht, Heinrich; Dörr, Helmuth-Günther; Reis, André; et al. (Human Mutation, 2015)
Numerous genes are involved in human growth regulation. Recently, autosomal-recessive inherited variants in centrosomal proteins have been identified in Seckel syndrome, primary microcephaly, or microcephalic osteodysplastic primary dwarfism. Common hallmarks of these syndromic forms are severe short stature and microcephaly. In a consanguineous family with two affected children with severe growth retardation and normocephaly, we used homozygosity mapping and next-generation sequencing to identify a homozygous MAP4 variant. MAP4 is a major protein for microtubule assembly during mitosis. High-expression levels in the somite boundaries of zebrafish suggested a role in growth and body segment patterning. The identified variant affects binding sites of kinases necessary for dynamic instability of microtubule formation. We found centrosome amplifications in mitotic fibroblast cells in vivo and in vitro. These numeric centrosomal aberrations were also present during interphase resulting in aberrant ciliogenesis. Furthermore, affected cells showed a dysfunction of the microtubule-dependent assembly of the Golgi apparatus, indicated by a significant lack of compactness of Golgi membranes. These observations demonstrated that MAP4 mutations contribute to the clinical spectrum of centrosomal defects and confirmed the complex role of a centrosomal protein in centrosomal, ciliary, and Golgi regulation associated with severe short stature.
EVALuna2:9244

Measurement of amniotic fluid steroids of midgestation via LC-MS/MS - Fahlbusch, Fabian B.; Heussner, Kirsten; Schmid, Matthias; Schild, Ralf; Rübner, Matthias; Hübner, Hanna; Rascher, Wolfgang; Dörr, Helmuth-Günther; Rauh, Manfred (Journal of Steroid Biochemistry and Molecular Biology, 2015)
Analysis of steroids by mass spectrometry (MS) has evolved into a reliable tool for the simultaneous detection of multiple steroids. As amniotic fluid (AF) and fetal serum composition of early pregnancy are closely related, the analysis of AF can yield information on the physiological status of the developing fetus. We evaluated the use of liquid-chromatography tandem mass spectrometry (LC-MS/MS) for AF steroid analysis, including the analysis of its sensitivity and accuracy for gender verification in healthy subjects.AF of 78 male and 94 female healthy newborns was analyzed by LC-MS/MS at 16 weeks of gestation. The levels of androstenedione, corticosterone, cortisol, cortisone, deoxycorticosterone, 11-deoxycortisol, dehydroepiandrosterone (DHEA), dehydroepiandrosterone-sulfate (DHEA-S), 17-hydroxyprogesterone, progesterone (17-OHP) and testosterone were measured. Steroid levels were compared to RIA and GC-MS levels of midgestation from the literature. Cross-validated logistic regression was used to obtain statistical predictions of gender at birth from testosterone and the above steroids.LC-MS/MS analysis of AF steroids yielded comparable results with published GC-MS data. Gender specific differences were found for androstenedione and testosterone concentrations with higher levels in the male fetus. In contrast to published RIA data no gender specific differences were observed for 17-hydroxyprogesterone and dehydroepiandrosterone AF concentrations. Testosterone concentrations yielded highly accurate predictions for male gender at birth. Additional analysis of further steroids did neither increase the accuracy, sensitivity nor specificity of this prediction. The estimated optimal cut-off value for amniotic testosterone level was 0.074 ?g/L for healthy male newborns.LC-MS/MS is a reliable method for the determination of steroids in amniotic fluid. The determination of testosterone in amniotic fluid by LC-MS/MS in early pregnancy of healthy subjects can be used to offer a reliable prediction of fetal gender at birth.
EVALuna2:17444

Medizinische Betreuung von jungen Frauen mit Ullrich-Turner-Syndrom in Deutschland - Dörr, Helmuth-Günther; Bettendorf, Markus; Binder, Gerhard; Braemswig, Juergen; Hauffa, Berthold P.; Holterhus, Paul-Martin; Mohnike, Klaus; Schmidt, Heinrich; Stalla, Guenter K.; Wabitsch, Martin; Woelfle, Joachim (Deutsche Medizinische Wochenschrift, 2020)
BACKGROUND: Many recommendations for medical care for women with Turner syndrome (TS) have been published in the past. There are no studies that analyse the care situation of the women in Germany until now. METHODS: The study was performed in 2015 based on a questionnaire that was completed by TS women (aged ≥ 18 years; median: 25 years). The questionnaire was devised by a French team and used with their permission. All women had received growth hormone treatment during childhood. The women were identified and addressed in writing through eleven cooperating centers and the support group. In all, 130 questionnaires were evaluated. RESULTS: 79 of the 130 women (61 %) stated that they had health problems. 38 % of the women were under medical care by only one physician and 42 % by two physicians. The gynecologist was mentioned most often (by 80.3 %), followed by the family physician (53.8 %). ENT was mentioned as a problem system by 35 %, but only 3 % of the women attended an ENT physician. The question as to whether at least one of the following examinations (measurements of blood pressure, blood sugar, blood fats, liver function and/or thyroid hormones, echocardiographic and/or audiogram examination) had been performed during a period of 4 years was answered as follows: blood pressure (85 %), blood sugar (47 %), blood fats (41 %), liver function (46 %), thyroid hormones (44 %), echocardiography (57 %) and audiogram (35 %). A comprehensive examination was performed in 9.8 % of the women. 103 women (80.5 %) received sexual hormone replacement therapy. 76 women were on further drugs; thyroid hormones (44 %) and antihypertensive drugs (11 %) were stated most often. CONCLUSIONS: This is the first study which analyses the current situation of medical care of TS women in Germany. Our data show that medical care of young adult TS women is not optimal. The study cannot clarify the reasons. Due to the numerous and different comorbidities, the medical care of TS women is complex and should therefore be provided multidisciplinarily by different specialists under the direction of one physician.
CRIS-Team Scopus Importer:2020-03-13

Miscarriages in families with an offspring that have classic congenital adrenal hyperplasia and 21-hydroxylase deficiency - Dörr, Helmuth-Günther; Hess, Johannes; Penger, Theresa; Marx, Martin; Oppelt, Patricia (BMC Pregnancy and Childbirth, 2018)
BACKGROUND: The most common form of congenital adrenal hyperplasia is 21-hydroxylase deficiency (CAH). Both men and women with classic CAH have lower fertility rates than the general population, and an increased rate of miscarriages has been reported in affected women. There are no data on the incidence rate of miscarriages in families with an offspring that have classic CAH. METHODS: We studied families with a history of classic CAH. The families came from different parts of Germany and attended the annual meeting of the German CAH support group for parents and patients which was held in Hamburg in September 2014. The data was collected anonymously by a paper-based questionnaire which was completed by the families at home. The families also accepted the responsibility to address this question to their siblings. In all, the data of 50 families with at least one child with classic CAH, and the data of 164 parental siblings were available for evaluation. Miscarriage rates were calculated in relation to the reported pregnancies. RESULTS: Twenty-two miscarriages were reported from 19 families. At least one miscarriage occurred in 38% of the families, three families experienced two miscarriages and 16 families had one miscarriage each. The mean miscarriage rate was 15.8%. The heterozygous mothers had a total of 90 siblings (41 m, 49 f), while 74 siblings (33 m, 41 f) were reported from the heterozygous fathers. The miscarriage rate was 10.1% in the families of the mothers` siblings, and 11.4% in the families of the fathers` siblings. The genotype was known in all parents that have an offspring with classic CAH, but not defined in 82% of the maternal siblings, and in 86% of the paternal siblings. No child with classic CAH has been diagnosed in any of the sibling's families to date. CONCLUSION: Our data show that the miscarriage rate in German families with a child with classic CAH is not elevated.
EVALuna2:35501

Mono-allelic deleterious variants in autosomal recessive skeletal dysplasia genes are strongly associated with idiopathic short stature - Thiel, C. T.; Hauer, Nadine; Vogl, C.; Uebe, Steffen; Sticht, Heinrich; Ekici, Arif Bülent; Kraus, Cornelia; Dörr, Helmuth-Günther; Reis, André (EUROPEAN JOURNAL OF HUMAN GENETICS, 2020)
CRIS-Team WoS Importer:2021-01-22

Oxygen-sensitive regulation and neuroprotective effects of growth hormone-dependent growth factors during early postnatal development - Jung, Susan; Boie, Gudrun; Dörr, Helmuth-Günther; Trollmann, Regina (American Journal of Physiology-Regulatory Integrative and Comparative Physiology, 2017)
Perinatal hypoxia severely disrupts metabolic and somatotrophic development, as well as cerebral maturational programs. Hypoxia-inducible transcription factors (HIFs) represent the most important endogenous adaptive mechanisms to hypoxia, activating a broad spectrum of growth factors that contribute to cell survival and energy homeostasis. To analyze effects of systemic hypoxia and growth hormone (GH) therapy (rhGH) on HIF-dependent growth factors during early postnatal development, we compared protein (using ELISA) and mRNA (using quantitative RT PCR) levels of growth factors in plasma and brain between normoxic and hypoxic mice (8% O2, 6 h; postnatal day 7, P7) at P14. Exposure to hypoxia led to reduced body weight (P < 0.001) and length (P < 0.04) compared with controls and was associated with significantly reduced plasma levels of mouse GH (P < 0.01) and IGF-1 (P < 0.01). RhGH abrogated these hypoxia-induced changes of the GH/IGF-1 axis associated with normalization of weight and length gain until P14 compared with controls. In addition, rhGH treatment increased cerebral IGF-1, IGF-2, IGFBP-2, and erythropoietin mRNA levels, resulting in significantly reduced apoptotic cell death in the hypoxic, developing mouse brain. These data indicate that rhGH may functionally restore hypoxia-induced systemic dysregulation of the GH/IGF-1 axis and induce upregulation of neuroprotective, HIF-dependent growth factors in the hypoxic developing brain.
EVALuna2:34028

Prenatal dexamethasone treatment for classic 21-hydroxylase deficiency in Europe - Nowotny, Hanna; Neumann, Uta; Tardy-Guidollet, Veronique; Faisal Ahmed, S.; Baronio, Federico; Battelino, Tadej; Bertherat, Jerome; Blankenstein, Oliver; Bonomi, Marco; Bouvattier, Claire; De la Perrière, Aude Brac; Brucker, Sara; et al. (European Journal of Endocrinology, 2022)
Objective: To assess the current medical practice in Europe regarding prenatal dexamethasone (Pdex) treatment of congenital adrenal hyperplasia (CAH) due to 21-hydroxylase defic iency. Design and methods: A questionnaire was designed and distributed, including 17 questions collecting quantitative and qualitative data. Thirty-six medical centres from 14 European countries responded and 30 out of 36 centres were reference centres of the European Reference Network on Rare Endocrine Conditions, EndoERN. Results: Pdex treatment is currently provided by 36% of the surveyed ce ntres. The treatment is initiated by different specialties, that is paediatricians, endocrinologists, gynaecologists or geneticists. Regarding the starting point of Pdex, 23% stated to initiate therapy at 4-5 weeks postconception (wpc), 31% at 6 wpc and 46 % as early as pregnancy is confirmed and before 7 wpc at the latest. A dose of 20 μg/kg/day is used. Dose distribution among the centres varies from once to thrice daily. Prenatal diagnostics for treated cases are conducted in 72% of the responding centres. Cases treated per country and year vary between 0.5 and 8.25. Registries for long-term follow-up are only available at 46% of the centres that are using Pdex treatment. National registries are only available in Sweden and France. Conclusions: This study reveals a high international variability and discrepancy in the use of Pdex treatment across Europe. It highlights the importance of a European cooperation initiative for a joint international prospective trial to establish evidence-based guidelines on prenatal diagnostics, treatment and follow-up of pregnancies at risk for CAH.
CRIS-Team Scopus Importer:2022-04-29

Psychometric properties of the quality of life in short statured youth (QoLISSY) questionnaire within the course of growth hormone treatment - Bloemeke, Janika; Silva, Neuza; Bullinger, Monika; Witt, Stefanie; Dörr, Helmuth-Günther; Quitmann, Julia (Health and Quality of Life Outcomes, 2019)
BackgroundThe Quality of Life of Short Stature Youth (QoLISSY) questionnaire is a patient- and parent-reported outcome measure assessing health-related quality of life (HRQOL) in short stature youth. This study evaluates the psychometric properties of the QoLISSY questionnaire within a German prospective trial of short statured children treated with human growth hormone (hGH).MethodThe instrument was administered to children with idiopathic growth hormone Deficiency (IGHD) and small for gestational age (SGA) before and after 12month of hGH treatment. Children with idiopathic short stature (ISS) served as a reference group receiving no treatment. Psychometric testing included scale distribution characteristics, reliability (internal consistency), criterion-and convergent validity (correlations with the generic KIDSCREEN-Index, inter-correlations among QOLISSY subscales), known-group validity (treatment status, height SDS), and responsiveness analysis (ability to detect change).ResultsOne hundred fifty-two parents and 66 children/adolescents completed both HRQOL assessments. The QoLISSY demonstrated good reliability with Cronbach's alpha > .70. Moderate significant correlations between QoLISSY domains and the KIDSCREEN-10 Index supported criterion validity. Statistically significant differences in HRQOL were observed between treatment groups at baseline with children who were about to start treatment reporting a significantly lower HRQOL compared to the children who will not receive treatment. No significant differences were found between the level of short stature based on height SDS scores ( -2 SDS, > -2 SDS). Furthermore, the instrument detected significant changes in HRQOL between the treated and the untreated group in patient-reports.ConclusionsIn conclusion, the scales showed satisfactory reliability, adequate validity and ability to detect change in self-reported HRQOL within GH treatment. Findings support QoLISSY's further use in clinical trials, offering the opportunity to adequately assess HRQOL from the patients' and caregivers' perspective to improve patient-centered care.
CRIS-Team WoS Importer:2019-04-04

Psychosocial health of girls and young women with UllrichTurner syndrome Psychosoziale gesundheit von mädchen und jungen frauen mit ullrich-turner-syndrom - Dörr, Helmuth-Günther; Oppelt, Patricia (Pädiatrische Praxis, 2019)
This paper gives an overview of neurocognitive, academic, social and psychological phenotypes of the UTS. In addition, the results of a survey on the life situation of young affected women in Germany after the end of growth hormone therapy are summarized using a paper questionnaire.
CRIS-Team Scopus Importer:2021-04-20
Keywords: Growth hormone; Psychosocial health; Quality of life; UTS

Quality of life of short-statured children born small for gestational age or idiopathic growth hormone deficiency within one year of growth hormone treatment - Quitmann, Julia; Bloemeke, Janika; Silva, Neuza; Bullinger, Monika; Witt, Stefanie; Akkurt, Ilker; Dunstheimer, Desirée; Vogel, Christian; Böttcher, Volker; Krahl, Ursula Kuhnle; Bettendorf, Markus; Schönau, Eckhard; et al. (Frontiers in Pediatrics, 2019)
Aside from clinical endpoints like height gain, health-related quality of life has also become an important outcome indicator in the medical field. However, the data on short stature and health-related quality of life is inconsistent. Therefore, we examined changes in health-related quality of life in German children with idiopathic growth hormone deficiency or children born small for gestational age before and after 12 months of human growth hormone treatment. Children with idiopathic short stature without treatment served as a comparison group. At baseline, health-related quality of life data of 154 patients with idiopathic growth hormone deficiency (n = 65), born small for gestational age (n = 58) and idiopathic short stature (n = 31) and one parent each was collected. Of these, 130 completed health-related quality of life assessments after 1-year of human growth hormone treatment. Outcome measures included the Quality of Life in Short Stature Youth questionnaire, as well as clinical and sociodemographic data. Our results showed that the physical, social, and emotional health-related quality of life of children treated with human growth hormone significantly increased, while untreated patients with idiopathic short stature reported a decrease in these domains. Along with this, a statistically significant increase in height in the treated group can be observed, while the slight increase in the untreated group was not significant. In conclusion, the results showed that human growth hormone treatment may have a positive effect not only on height but also in improving patient-reported health-related quality of life of children with idiopathic growth hormone deficiency and children born small for gestational age.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Growth hormone treatment; Health-related quality of life; IGHD; ISS; QoLISSY; Short stature

Quality of life of young adults after a growth hormone therapy with childhood onset - Quitmann, J. H.; Rohenkohl, A. C.; Kammerer, U.; Schöfl, Christof; Bullinger, M.; Dörr, Helmuth-Günther (Deutsche Medizinische Wochenschrift, 2014)
Little is known about the health-related quality of life of young adults with childhood onset idiopathic growth hormone deficiency or neurosecretory dysfunction of growth hormone secretion, who have been treated with recombinant human growth hormone (GH).Patients were diagnosed and treated with human growth hormone at the University Children´s Hospital in Erlangen (n=85). The data of both groups were merged for analysis, because no difference between idiopathic growth hormone deficiency and neurosecretory dysfunction of growth hormone secretion in auxological. Data were found. Health-related quality of life was cross- sectionally assessed after the end of growth hormone therapy with the Short Form-36 Health Survey and the Nottingham Health Profiles for which population based norm data are available.At the time of the survey, the patients (53 m, 32 f) were 23.5 ± 4.6 years old. At start of GH therapy, age was 10.5 ± 2.8 and at the end 16.3 ± 1,4 years. At start, height SDS was -3.20 ± 1.06. GH dose was 0,026 ± 0,012 mg/kg/d (daily s. c.-injections). The increase in height SDS after the end of GH therapy was 1.69 ± 1.22. Compared to the reference population, patients reported significantly lower scores on the scales energy level, vitality, social functioning, indicating a greater social isolation, a stronger emotional reaction, an increased loss of mobility and a worse psychological state.Young adults report specific impairments after completion of GH therapy.
EVALuna2:1888

Quality of Survival and Growth in Children and Young Adults in the PNET4 European Controlled Trial of Hyperfractionated Versus Conventional Radiation Therapy for Standard-Risk Medulloblastoma - Kennedy, Colin; Bull, Kim; Chevignard, Mathilde; Culliford, David; Dörr, Helmuth-Günther; Doz, Francois; Kortmann, Rolf-Dieter; Lannering, Birgitta; Massimino, Maura; Navajas Gutierrez, Aurora; Rutkowski, Stefan; Spoudeas, Helen A.; et al. (International Journal of Radiation Oncology Biology Physics, 2014)
To compare quality of survival in "standard-risk" medulloblastoma after hyperfractionated radiation therapy of the central nervous system with that after standard radiation therapy, combined with a chemotherapy regimen common to both treatment arms, in the PNET4 randomised controlled trial.Participants in the PNET4 trial and their parents/caregivers in 7 participating anonymized countries completed standardized questionnaires in their own language on executive function, health status, behavior, health-related quality of life, and medical, educational, employment, and social information. Pre- and postoperative neurologic status and serial heights and weights were also recorded.Data were provided by 151 of 244 eligible survivors (62%) at a median age at assessment of 15.2 years and median interval from diagnosis of 5.8 years. Compared with standard radiation therapy, hyperfractionated radiation therapy was associated with lower (ie, better) z-scores for executive function in all participants (mean intergroup difference 0.48 SDs, 95% confidence interval 0.16-0.81, P=.004), but health status, behavioral difficulties, and health-related quality of life z-scores were similar in the 2 treatment arms. Data on hearing impairment were equivocal. Hyperfractionated radiation therapy was also associated with greater decrement in height z-scores (mean intergroup difference 0.43 SDs, 95% confidence interval 0.10-0.76, P=.011).Hyperfractionated radiation therapy was associated with better executive function and worse growth but without accompanying change in health status, behavior, or quality of life.
EVALuna2:18860

Recombinant Human Growth Hormone Activates Neuroprotective Growth Factors in Hypoxic Brain Injury in Neonatal Mice - Jung, Susan; Terörde, Klara; Dörr, Helmuth-Günther; Trollmann, Regina (Endocrinology, 2021)
Perinatal hypoxia severely disrupts cerebral metabolic and maturational programs beyond apoptotic cell death. Antiapoptotic treatments such as erythropoietin are suggested to improve outcomes in hypoxic brain injury; however, the results are controversial. We analyzed the neuroprotective effects of recombinant human growth hormone (rhGH) on regenerative mechanisms in the hypoxic developing mouse brain in comparison to controls. Using an established model of neonatal acute hypoxia (8% O2, 6 hours), P7 mice were treated intraperitoneally with rhGH (4000 µg/kg) 0, 12, and 24 hours after hypoxic exposure. After a regeneration period of 48 hours, expression of hypoxia-inducible neurotrophic factors (erythropoietin [EPO], vascular endothelial growth factor A [VEGF-A], insulin-like growth factors 1 and 2 [IGF-1/-2], IGF binding proteins) and proinflammatory markers was analyzed. In vitro experiments were performed using primary mouse cortical neurons (E14, DIV6). rhGH increased neuronal gene expression of EPO, IGF-1, and VEGF (P < .05) in vitro and diminished apoptosis of hypoxic neurons in a dose-dependent manner. In the developing brain, rhGH treatment led to a notable reduction of apoptosis in the subventricular zone and hippocampus (P < .05), abolished hypoxia-induced downregulation of IGF-1/IGF-2 expression (P < .05), and led to a significant accumulation of endogenous EPO protein and anti-inflammatory effects through modulation of interleukin-1β and tumor necrosis factor α signaling as well as upregulation of cerebral phosphorylated extracellularly regulated kinase 1/2 levels (ERK1/2). Indicating stabilizing effects on the blood-brain barrier (BBB), rhGH significantly modified cerebrovascular occludin expression. Thus, we conclude that rhGH mediates neuroprotective effects by the activation of endogenous neurotrophic growth factors and BBB stabilization. In addition, the modification of ERK1/2 pathways is involved in neuroprotective actions of rhGH. The present study adds further evidence that pharmacologic activation of neurotrophic growth factors may be a promising target for neonatal neuroprotection.
CRIS-Team Scopus Importer:2021-03-05
Keywords: apoptosis; BBB; IGF binding proteins; IGF-1; IGF-2; interleukin-1β; neuroprotection; occludin; pERK 1/2; TNF-α; VEGF

Response to Letter to the Editor From Viru-Loza and Chavez-Nomberto: "Safety and Efficacy of Pediatric Growth Hormone Therapy: Results From the Full KIGS Cohort " - Maghnie, Mohamad; Ranke, Michael B.; Geffner, Mitchell E.; Vlachopapadopoulou, Elpis; Ibanez, Lourdes; Carlsson, Martin; Cutfield, Wayne; Rooman, Raoul; Gomez, Roy; Wajnrajch, Michael P.; Linglart, Agnes; Stawerska, Renata; et al. (Journal of Clinical Endocrinology and Metabolism, 2023)
CRIS-Team WoS Importer:2023-03-17

Results from an international multicenter trial evaluating the ease-of-use of and preference for a newly developed disposable injection pen for the treatment of growth hormone deficiency in treatment-naïve children and adults - Pleil, Andreas M.; Darendeliler, Feyza; Dörr, Helmuth-Günther; Hutchinson, Katherine; Wollmann, Hartmut A. (Medical Devices : Evidence and Research, 2014)
Previous research has reported that ease of use of and preference for a delivery device are associated with greater patient compliance - an important factor in achieving optimal therapeutic results. The objective of this study was to assess the ease-of-use of a new disposable pen (GoQuick(®), Pfizer, Inc.) versus the current reusable pen (GENOTROPIN Pen(®), Pfizer, Inc.) to inject a daily dose of recombinant DNA origin human growth hormone, Genotropin(®) (somatropin) in standard practice. In this randomized, crossover, multicenter, multinational, open-label study, ease-of-use of and preference for the two pens were assessed in three treatment-naïve populations: 1) parents of very young children; 2) parent-child dyads; and 3) adults via use of a validated self-report Injection Pen Assessment Questionnaire (IPAQ) after 2 months of at-home-use experience. The primary endpoint was the proportion of participants who reported the new disposable pen to be no different from or easier to use than the current reusable pen. Safety was also assessed and reported according to local legal requirements. Of the 120 screened patients, 119 were included in the ease-of-use analysis and all were included in the safety analyses. In all, 67.2% found the new somatropin disposable pen to be no different from or easier to use than the reusable pen (95% confidence interval: 58.8-75.7). Most adverse events were mild or moderate. No deaths or device- or treatment-related serious adverse events were reported. These results suggest that improvements made to the reusable somatropin pen are tangible and recognizable to treatment-naïve patients and their caregivers, child-caregiver dyads, and adults, and may positively impact continued compliance with therapy.ClinicalTrials.gov identifier: NCT01112865.
EVALuna2:18887

Safety and effectiveness of pediatric growth hormone therapy: Results from the full cohort in KIGS - Maghnie, Mohamad; Ranke, Michael B.; Geffner, Mitchell E.; Vlachopapadopoulou, Elpis; Dörr, Helmuth-Günther; Wikland, Kerstin Albertsson; Ibanez, Lourdes; Carlsson, Martin; Cutfield, Wayne; Rooman, Raoul; Gomez, Roy; Wajnrajch, Michael P.; et al. (HORMONE RESEARCH IN PAEDIATRICS, 2021)
CRIS-Team WoS Importer:2021-10-08

Sex chromosome DSD individuals with mosaic 45,X0 and aberrant Y chromosomes in 46,XY cells: distinct gender phenotypes and germ cell tumour risks§ - Vogt, Peter H.; Besikoglu, Banu; Bettendorf, Markus; Frank-Herrmann, Petra; Zimmer, Jutta; Bender, Urike; Knauer-Fischer, Sabine; Choukair, Daniela; Sinn, Peter; Dörr, Helmuth-Günther; Wölfle, Joachim; Heidemann, Peter H.; et al. (Systems Biology in Reproductive Medicine, 2022)
“Differences of Sexual Development (DSD),” individuals with rearranged Y chromosome breaks in their 46,XY cells are reported with male and female gender phenotypes and differences in germ cell tumour (GCT) risk. This raised the question of whether male or female gender and GCT risk depends on the site of the break and/or rearrangement of the individual´s Y chromosome. In this paper, we report molecular mapping of the breakpoint on the aberrant Y chromosome of 22 DSD individuals with a 45,X/46,XY karyotype reared with a different gender. Their Y chromosome breaks are found at different sites on the long and short Y arms. Our data indicate that gender rearing is, neither dependent on the site of Y breakage, nor on the amount of 45,X0 cells in the individuals' leukocytes. Most prominent are secondary rearrangements of the Y chromosome breaks forming di-centric Y-structures (“dic-Y”). Duplications of the short Y arm and the proximal part of the long Y arm are the results. A putative GCT risk has been analysed with immunohistochemical experiments on some dysgenetic gonadal tissue sections. With specific antibodies for OCT3/4 expression, we marked the pluripotent germ cell fraction being potential tumour precursor cells. With specific antibodies for DDX3Y, TSPY, and UTY we analyzed their putative Gonadoblastoma Y (GBY) tumour susceptibility function in the same specimen. We conclude GBY expression is only diagnostic for GCT development in the aberrant germ cells of these DSD individuals when strong OCT3/4 expression has marked their pluripotency.
CRIS-Team Scopus Importer:2022-05-27
Keywords: 45X/46XY mosaic DSD; di-centric Y chromosome; Germ cell tumour risk; OCT3/4 expression GBY expression

Short Children with CHARGE Syndrome: Do They Benefit from Growth Hormone Therapy? - Dörr, Helmuth-Günther; Boguszewski, Margaret; Dahlgren, Jovanna; Dunger, David; Geffner, Mitchell E.; Hokken-Koelega, Anita C.; Lindberg, Anders; Polak, Michel; Rooman, Raoul (Hormone Research in Paediatrics, 2015)
The aim of this study was to evaluate the response to recombinant growth hormone (GH) treatment in short children with CHARGE syndrome.We identified 51 children (28 boys and 23 girls) in KIGS (Pfizer International Growth Database). The median chronological age was 7.6 years at the start of GH therapy and 13.2 years at the latest visit. Evaluation for GH deficiency (n = 33) was based on the following: peak GH level 7.3 ?g/l and IGF-I level -2.01 standard deviation score (SDS). Sixteen subjects (9 boys) were followed longitudinally for 2 years.Birth length (median SDS, -0.47) and weight (-0.97) were slightly reduced. At the start of GH therapy, height was -3.6 SDS, BMI -0.7 SDS, and the GH dose was 0.26 mg/kg/week. At the latest visit after 2.7 years of GH therapy, height had increased to -2.2 SDS and BMI to -0.5 SDS. In the longitudinal group, height increased from -3.72 SDS at the start of GH therapy to -2.92 SDS after 1 year to -2.37 SDS after 2 years of therapy (start - 2 years: p < 0.05), height velocity increased from -1.69 to 2.98 to 0.95 SDS, and BMI and GH dose (mg/kg/week) remained almost unchanged.Our data show a positive effect of conventional doses of GH on short-term growth velocity for the longitudinal as well as for the total group, without any safety issues.
EVALuna2:18915

Short-term adverse effects of testosterone used for priming in prepubertal boys before growth hormone stimulation test - Albrecht, Andrea; Penger, Theresa; Marx, Martin; Hirsch, Karin; Dörr, Helmuth-Günther (Journal of Pediatric Endocrinology & Metabolism, 2018)
BACKGROUND: Despite the fact that priming with sex steroids in prepubertal children before growth hormone (GH) provocative tests is recommended, there is an ongoing controversial discussion about the appropriate age of the children, the drug used for priming, the dose and the period between priming and the GH test. Interestingly, there is no discussion on the safety of this procedure. To date, only little data have been available on the possible side effects of priming with testosterone. METHODS: We analyzed the outcome in 188 short-statured prepubertal boys who had been primed with testosterone enanthate (n=136: 50 mg; n=51: 125 mg, and accidentally one boy with 250 mg) 7 days prior to the GH test. Serum testosterone levels were measured on the day of the GH test in 99 boys. RESULTS: Overall, only five boys developed adverse side effects. Two boys (dose 125 mg) showed severe low-flow priapism and had to undergo decompression of the corpora cavernosa. One boy suffered from self-limiting priapism and testicular pain (dose 50 mg). Two patients reported testicular pain (each dose 50 mg). The single patient with 250 mg testosterone did not show any adverse effects. The total side effect rate was 2.7%. The serum testosterone levels of the boys with side effects were not different from the testosterone levels of the boys without any side effects. CONCLUSIONS: Parents and patients should be informed about the possible side effects of priming with testosterone such as priapism and testicular pain. However, the overall side effect rate is low. We found no correlation between the outcome and the testosterone dose used and/or the level of serum testosterone.
EVALuna2:35502

Spontaneous postnatal growth is reduced in children with CHARGE syndrome - Dörr, Helmuth-Günther; Madeja, Julia; Junghans, Claudia (Acta Paediatrica, 2015)
There is a scarcity of data on postnatal growth in children with CHARGE syndrome, a genetic disorder. This study analysed spontaneous growth and weight in German children with CHARGE from birth to the age of 6 years.This was a retrospective analysis of 19 children, nine females and 10 males, using data from child health records. Standard deviation scores (SDS) were calculated based on Swiss references.The median birthweight was 2950 g (-0.78 SDS), and the birth length was 49 cm (-0.5 SDS). There was a significant loss of median body length, at around 4 weeks of age from -0.5 to -2.3 SDS (p < 0.05). At 1 year, the median length was -2.6 SDS and it remained low until 5 years of age when the lowest value was found to be -2.8 SDS. There was a significant increase in median body mass index (BMI) from -1.15 SDS at 1 year to -0.15 SDS at 5 years (p < 0.01).Children with CHARGE syndrome displayed almost normal length and weight data at birth, with just one of the 19 infants having below average length for gestational age. However, postnatal growth was retarded during infancy and childhood, and the increase in BMI-SDS did not correlate with growth.
EVALuna2:18914

The placental mTOR-pathway: correlation with early growth trajectories following intrauterine growth restriction? - Fahlbusch, F. B.; Menendez-Castro, C.; Nögel, Stephanie; Marek, I.; Beckmann, Matthias; Schleussner, E.; Ruebner, M.; Huebner, H.; Dörr, Helmuth-Günther; Schild, R. L.; Doetsch, J.; Rascher, Wolfgang; et al. (Journal of Developmental Origins of Health and Disease, 2015)
Idiopathic intrauterine growth restriction (IUGR) is a result of impaired placental nutrient supply. Newborns with IUGR exhibiting postnatal catch-up growth are of higher risk for cardiovascular and metabolic co-morbidities in adult life. Mammalian target of rapamycin (mTOR) was recently shown to function as a placental nutrient sensor. Thus, we determined possible correlations of members of the placental mTOR signaling cascade with auxologic parameters of postnatal growth. The protein expression and activity of mTOR-pathway signaling components, Akt, AMP-activated protein kinase ?, mTOR, p70S6kinase1 and insulin receptor substrate-1 were analysed via western blotting in IUGR v. matched appropriate-for-gestational age (AGA) placentas. Moreover, mTOR was immunohistochemically stained in placental sections. Data from western blot analyses were correlated with retrospective auxological follow-up data at 1 year of age. We found significant catch-up growth in the 1st year of life in the IUGR group. MTOR and its activated form are immunohistochemically detected in multiple placental compartments. We identified correlations of placental mTOR-pathway signaling components to auxological data at birth and at 1 year of life in IUGR. Analysis of the protein expression and phosphorylation level of mTOR-pathway components in IUGR and AGA placentas postpartum, however, did not reveal pathognomonic changes. Our findings suggest that the level of activated mTOR correlates with early catch-up growth following IUGR. However, the complexity of signals converging at the mTOR nexus and its cellular distribution pattern seem to limit its potential as biomarker in this setting.
EVALuna2:17439

Variable White Matter Atrophy and Intellectual Development in a Family With X-linked Creatine Transporter Deficiency Despite Genotypic Homogeneity - Heussinger, Nicole; Saake, Marc; Mennecke, Angelika; Dörr, Helmuth-Günther; Trollmann, Regina (Pediatric Neurology, 2017)
The X-linked creatine transporter deficiency (CRTD) caused by an SLC6A8 mutation represents the second most common cause of X-linked intellectual disability. The clinical phenotype ranges from mild to severe intellectual disability, epilepsy, short stature, poor language skills, and autism spectrum disorders. The objective of this study was to investigate phenotypic variability in the context of genotype, cerebral creatine concentration, and volumetric analysis in a family with CRTD.The clinical phenotype and manifestations of epilepsy were assessed in a Caucasian family with CRTD. DNA sequencing and creatine metabolism analysis confirmed the diagnosis. Cerebral magnetic resonance imaging (cMRI) with voxel-based morphometry and magnetic resonance spectroscopy was performed in all family members.An SLC6A8 missense mutation (c.1169C>T; p.Pro390Leu, exon 8) was detected in four of five individuals. Both male siblings were hemizygous, the mother and the affected sister heterozygous for the mutation. Structural cMRI was normal, whereas voxel-based morphometry analysis showed reduced white matter volume below the first percentile of the reference population of 290 subjects in the more severely affected boy compared with family members and controls. Normalized creatine concentration differed significantly between the individuals (P < 0.005).There is a broad phenotypic variability in CRTD even in family members with the same mutation. Differences in mental development could be related to atrophy of the subcortical white matter.
EVALuna2:14646